No ingested micro- and macro-plastics detected in three shark species from the Bass Strait, Australia - Varun Nadesh; Alexander L. Bond; Jennifer L. Lavers (Marine Pollution Bulletin, 2026)

Replacing maize grain with self-fermented agro-waste in total mixed ration improves fatty acid profile, oxidative stability and meat quality traits in goats - Rajat Bagdas; Gauri Jairath; Varun; Suman Bishnoi; Yashavanth Basavapatna Subbanna; Gorakh Mal; Ashim K. Biswas; Triveni Dutt; Arup Ratan Sen; Randhir Singh Bhatt; Lalit Kumar Soni; Birbal Singh; et al. (Meat Science, 2026)

A theoretical evaluation of cyclostrophic balance in the Venusian atmosphere using the Venus Planetary Climate Model - Jayadev Pradeep; S.V. Sunilkumar; N. Koushik; Varun Nikam; K.R. Lakshmi; S. Sijikumar; K. Kishore Kumar; Govindan Kutty (Icarus, 2026)

Mechanistic insights into Cu impurity retention and its effective removal in direct recycling of lithium-ion batteries - Wenlin Yan; Wei Li; Qiushi Miao; Mengchen Liu; Ershuang Lu; Jiao Lin; Minji Lee; Haichen Lin; Shuangjie Tan; Varun Gupta; Zheng Chen; Ping Liu (Chemical Engineering Journal, 2026)

Unpaid caregiving, care-related travel, and gendered time poverty: Evidence from India’s national time-use survey - G M Hridya; Apoorva Singh; Agnivesh Pani; Varun Varghese (Travel Behaviour and Society, 2026)

Green synthesis of biomass derived zinc-ferrite bimetallic nanoparticles and their catalytic applications to access bioactive nitrogenous heterocyclic scaffolds - Ekta Bala; Ankit Kachore; Varun Aggarwal; Hemant Singh; Ishika Sharma; Himanshu; Rohit Sharma; Saima; Rakesh Kumar; Kasim Sakran Abass; Praveen Kumar Verma (Journal of Environmental Chemical Engineering, 2026)

Highly dispersed Cu on TiO₂ for photoreduction of hexavalent chromium in the presence of glycerol - Srishti; Shweta Kumari; Sumit Kumar Pathak; Abhishikta Chatterjee; Varun Kumar Gupta; Aditya Kumar; Apurba Sinhamahapatra (Journal of Environmental Chemical Engineering, 2026)

Characteristics of the stable and convective boundary layer on Mars during a global dust storm year - Varun Sheel; Tirtha J. Kalita; S. Rafkin (Icarus, 2026)

Experimental evidence for metallic melt trapping in the deep Martian mantle – Implications for inefficient melt segregation and highly siderophile element retention - Kyusei Tsuno; Hideharu Kuwahara; Varun Manilal; Axel Wittmann; Kurt Leinenweber; Tetsuo Irifune; Damanveer S Grewal (Earth and Planetary Science Letters, 2026)

Acitretin shows promising potential in Alzheimer’s disease: retinoid-driven modulation of amyloid processing, neuroinflammation, and translational prospects - Varun Sharma; Kanika Vashisht; Garima Choudhary; Vaishali Choudhay; Vandana Bhatia; Mahendra Singh Ashawat; Ashish Baldi; Shiv Kumar Kushawaha (Inflammopharmacology, 2026)

An analytical model for subsurface ground motions due to kinematic shear dislocation sources in layered media - Jahnabi Basu; B Shree Rashmi; S.T.G. Raghukanth; Varun Kumar Singla (Soil Dynamics and Earthquake Engineering, 2026)

Effect of uncertainties in the electron temperature on the topside Venus ionosphere - Satyandra M. Sharma; Varun Sheel (Icarus, 2026)

Real-time traffic congestion detection using smartphone multi-sensor data and stacked ensemble learning - Ritesh Kumar; Varun Singh; Shahrukh (Innovative Infrastructure Solutions, 2026)

Predictive modelling of soil organic carbon, carbon stocks, and fractions across elevation gradients in the dry-temperate region of North-West Himalaya - Varun Parmar; Rushali Katoch; Naveen Datt; Pardeep Kumar; Ranbir Singh Rana; Narender Kumar Sankhyan; Rishi Mahajan; Justin George Kalambukattu (Environmental Monitoring and Assessment, 2026)

Soil Carbon Dynamics and Microbiological Properties as Influenced by Integrated Phosphorus Management in Acid Alfisol - Dhanbir Singh; Rewangini Ranjha; Sanjay K. Sharma; Varun Parmar (Journal of Soil Science and Plant Nutrition, 2026)

Supplementation with minerals and multi-strain probiotics attenuate neonatal piglet mortality, improve growth rate and augment systemic and mucosal immune parameters - Sakshi; Ujjwal Kumar De; Anju Kala; Varun Kumar Sarkar; Amit Kumar; Anuj Chauhan; Narayana Rathode (Veterinary Immunology and Immunopathology, 2026)

Percolative core formation in oxidized planetesimals – I: experiments on melt migration in olivine aggregates - Varun Manilal; Kyusei Tsuno; Hideharu Kuwahara; Axel Wittmann; Anne Pommier; Christy Till; Damanveer S. Grewal (Geochimica et Cosmochimica Acta, 2026)

A new paradigm in Parkinson’s disease: kidney-origin α-synuclein pathology driven by PKC signaling and aurothioglucose - Kanika Vashisht; Varun Sharma; Mahendra Singh Ashawat; Ashish Baldi; Shiv Kumar Kushawaha (Inflammopharmacology, 2026)

From glycemic control to neuroprotection: alogliptin as a repurposed candidate for Huntington’s disease - Garima Choudhary; Kanika Vashisht; Varun Sharma; Mahendra Singh Ashawat; Shiv Kumar Kushawaha (Metabolic Brain Disease, 2026)

Repurposing apremilast for alzheimer’s disease: multitarget modulation of cAMP‑PI3K/Akt–GSK‑3β and NF‑κB signaling - Nitish Choudhary; Shakshi Rana; Kanika Vashisht; Varun Sharma; Vandana Bhatia; Mahendra Singh Ashawat; Shiv Kumar Kushawaha (Metabolic Brain Disease, 2026)

Isolation, characterization, and proof of concept evaluation of serially adapted bacteriophages against multidrug-resistant Escherichia coli - Varun Rathi; Prakash R. Nayak; Namdeo R. Bulbule; Milind M. Chawak; Atharva Poundarik (Folia Microbiologica, 2026)

Aqueous Brilliant Blue adsorption on Fe3O4@Kaolin: Adsorption Performance, Equilibrium, and Operational Parameters - Daniel Olabode Oguntuyi; Olalekan Olabode; Christiana Eziashi; Wykendrick Jones; Akintayo Emmanuel Ariwoola; Varun Paul; Charles U Pittman; Todd Mlsna (Journal of Environmental Sciences, 2026)

Irrigation reshapes desert avifauna: Shifts in composition, guild structure and density of birds in irrigated croplands of the Thar Desert - Varun Kher; Sutirtha Dutta (Journal of Arid Environments, 2026)

Spatiotemporal targeting of miR-125b-5p regulatory hub via dual-ligand nanocarriers to polarize tumor-associated macrophages towards tumoricidal phenotype in breast cancer microenvironment - Garima Sharma; Ashish Ranjan Sharma; Varun Dewaker; Songrae Kim; Hoibin Jeong; Jin-Chul Kim (Chemical Engineering Journal, 2026)

Safeguarding the role of humans in conservation science in the age of AI - Amanda E. Bates; Bea Maas; Vanessa M. Adams; John F. Benson; Dominick A. DellaSala; Arash Ghoddousi; Varun R. Goswami; Janice Ser Huay Lee; Javier Nori; Valeria Rinaudo; Xingfeng Si; Orsolya Valkó; et al. (Biological Conservation, 2026)

Updated Recommendations for the Bioanalysis of Antibody–Drug Conjugates (ADC) from the ADC working group of the AAPS Bioanalytical Community - Jim X. Shen; Robert Dodge; Shoshana Oberstein; Jennifer Cunliffe; Varun Ramani; Soumya Mohana Sundaram; Ines C. Santos; Chongwoo Yu; Sanjay L. Dholakiya; Seema Kumar; Xiaohui Sophia Xu; Sasha Fraser; et al. (The AAPS Journal, 2026)
Antibody–drug conjugates (ADCs) represent a rapidly evolving therapeutic modality, combining the selective targeting of monoclonal antibodies with highly potent small molecule payloads. Their inherent structural complexity demands a sophisticated and multi-faceted bioanalytical approach spanning preclinical discovery through late-stage clinical development. This white paper, developed by the ADC Working Group of the AAPS bioanalytical community, comprising over 100 members from industry, contract research organizations (CROs), and regulatory agencies, provides updated recommendations for ADC bioanalysis. Building upon the foundational 2013 AAPS position paper and recent publications governing regulatory frameworks on PK considerations, this work addresses advances in bioanalytical quantitation strategies for total antibody (tAb), conjugated ADC, free (unconjugated) payload, and drug-to antibody ratio (DAR); novel immunogenicity assessment considerations; soluble target interference; critical reagent lifecycle management; payload-specific stability requirements; cross-validation strategies; and regulatory considerations. The recommendations presented herein reflect over a decade of scientific progress and are designed to serve as a comprehensive, empirically validated, and industry aligned bioanalytical framework for contemporary ADC drug development.

A Narrative Summary of Strategies to Mitigate Intradialytic Hypotension in Poisoned Patients Requiring Extracorporeal Toxin Elimination - David K. Carroll; Andrew M. King; Andrew Isaacson; Brandtly Yakey; Aria Darling; Varun Vohra; Josh D. King (Journal of Medical Toxicology, 2026)

Trace element accumulation and ecological risk in agricultural and recreational pond sediments near a coal-fired power plant - Charles Bills; Varun G. Paul; Prashan M. Rodrigo; Todd E. Mlsna (Environmental Geochemistry and Health, 2026)

Modelling state-level crash fatalities by a network-constrained inhomogeneous poisson point process - Pengyu Chen; Xiuchuan Liu; Sicheng Wang; Ting Fung Ma; Xunan Yang; Varun Goel (Applied Geography, 2026)

Dissecting genetic variability and trait interrelationship in open condition under heat stress in tomato (Solanum lycopersicum L.) for fruit yield and seed production - B. H. Varun; Rajinder Singh; S. K. Jindal; Jyoti Singh; Nirankar Verma (Vegetos, 2026)
Tomato is sensitive to high temperature which effects vegetative as well as reproductive behavior. The present study was conducted in 2020 and 2021 using 76-diverse tomato genotypes, during summer months in Ludhiana, Punjab conditions where temperature is persistently high i.e., more than 35 °C which is detrimental for tomato production. The genotypes were evaluated based on 17 traits which included vegetative, reproductive and biochemical traits. Genetic parameters (PCV, GCV, heritability, genetic-advance), and multivariate analysis (correlation and path-analysis) were used to assess the diversity and trait association of the genotypes. Paired-ANOVA showed significant differences among genotypes for all traits, confirming ample genetic variability. High heritability coupled with high genetic-advance for pollen viability, number of fruits, and fruit yield per plant, suggesting additive gene action. Pollen-viability reduced considerably in the susceptible genotypes where the viability reduced to less than 60% contrastingly tolerant genotypes retained more than 80% viability. These findings provide critical insights for breeders to develop heat-resilient genotypes through targeted selection and genetic improvement strategies. Correlation showed that fruit yield and seed yield was strongly and positively associated with number of fruits ( r = 0.35), pollen viability ( r = 0.20) and seed yield ( r = 0.33), while negatively correlated with number of days to anthesis ( r = – 0.25) and dry matter content ( r = – 0.18), indicating the advantage of early flowering during heat stress. Path-analysis showed that number of fruits (0.50) and number of seeds (0.35) had positive association with fruit and seed yield while days to anthesis showed strong negative effects, confirming that reproductive efficiency traits are the most reliable targets for improving yield in heat-stressed tomato.

Optimizing and understanding complex relationships between micro-inertia and spin gradient viscosity in off-centered stagnation point flow - Vishwanatha R. Banakar; K. Karthik; Shakti Prakash Jena; R.S. Varun Kumar (Dynamics of Atmospheres and Oceans, 2026)

First ADME profile of fentanyl (437-38-7) - synthetic opioid driving overdose epidemics: Comprehensive in silico studies for clinical and forensic applications - Łukasz Niżnik; Oktawia Fijałkowska; Varun Ahuja; Gowrav Adiga Perdur; Kamil Jurowski (Chemico-Biological Interactions, 2026)

Design and Development of Myco-Mediated Bioremediation System for the Treatment of Runoff and Grey Water - Anupam Barh; Uday Mandal; J. M. S. Tomar; Deepak Singh; Varun Chauhan; Sudheer Kumar Annepu; Rama Pal; M. Muruganandam; Trisha Roy; A. C. Rathore; A. K. Gupta; Devideen Yadav; et al. (Water, Air, & Soil Pollution, 2026)

Exploring the application of various condenser microphones for wrist pulse measurement using machine learning models - Chetna Sharma; Neha; Gurinderjit Singh; Yogesh Kumar; Varun Dhiman; Sanjeev Kumar (Physical and Engineering Sciences in Medicine, 2026)

Macro to nano-scale landslide susceptibility zonation and analysis: insights from the 2024 Shirur landslide - Priyajit Kundu; Varun Menon; Sreevalsa Kolathayar; Pruthviraj Umesh (Bulletin of Engineering Geology and the Environment, 2026)

Spatial analysis and hybrid machine learning prediction of forest fire susceptibility: a longitudinal appraisal synergy with physiographic division - Netrananda Sahu; Pritiranjan Das; Prince Gupta; Suraj Kumar Mallick; Rajiv Pandey; Xiaojun Wang; Manish Kumar; Ayush Varun; Ravi Kesharwani; Anil Kumar (Advances in Space Research, 2026)

Identification and characterization of the topside bulge of the Venusian ionosphere - Satyandra M. Sharma; Varun Sheel; Martin Pätzold (Icarus, 2026)

The Impact of Earthquake Swarms Occurred in the South Scotia Sea over Antarctica and South America - A. Akilan; H. Schuh; C. Varun; G. G. Krishna Teja; Sravan Kumar Kotluri; T. T. Charan; M. Satyanarayanan; H. V. S. Satyanarayana (Pure and Applied Geophysics, 2026)

Deciphering temporal biochemical dimensions of Alternaria brassicicola resistance mechanism in cauliflower using multivariate analysis - Varun B. H.; Shrawan Singh; Vinay Verma; Bhag Chand Shivran; Sushma Sagar; Manisha Mangal; Anil Khar; Lakshman Prasad; Navinder Saini (European Journal of Plant Pathology, 2026)

Therapeutic milestones against multidrug resistant Acinetobacter baumannii: from legacy antibiotics to Zosurabalpin - Jaya Malik; Shilpy Singh; Dharmsheel Shrivastav; Ved Vrat Verma; Ravi Kant Pal; Manoj Kumar Mishra; Varun Kumar Sharma (Archives of Microbiology, 2026)

Climate change impacts on vegetation dynamics and transhumant pastoralism in the Western Himalayas - Netrananda Sahu; Ravi Kesharwani; Yogeshwar Singh Rathore; Anil Kumar; Ayush Varun; Martand Mani Mishra; Pritiranjan Das; Basanta K. Das; Suraj Kumar Mallick (Environmental Monitoring and Assessment, 2026)

A deep learning mobile application for tomato leaf nutrition deficiency identification with YOLOv8 and enhanced augmentation - Kamaldeep Joshi; Varun Kumar; Sumit Kumar; Kriti Katyal; Rainu Nandal; Ashima Nehra; Kashmir Singh; Narendra Tuteja; Ritu Gill; Sarvajeet Singh Gill (Plant Science, 2026)

Carbon capture from ArcelorMittal hot briquetted Iron plant using air liquide cryocap™ FG technology – FEED study - Sebastiano Giardinella; Varun Gopalakrishnan; Vincent Gueret; Lindsey Turney; Vincent Lu; Chris Tovee; David Zybko; Marcelo Andrade; Christopher Harris; Pierre-Philippe Guerif; Timothy Henderson; Anderson Morelato; et al. (International Journal of Greenhouse Gas Control, 2026)

Effect of strategic supplementations of antioxidant multiminerals and vitamins to transitional buffaloes on serum biochemistry, non-esterified fatty acid and calf health - Desh Deepak; Ujjwal Kumar De; Tarun Kumar Sarkar; Gulab Chandra; Varun Kumar Sarkar (Tropical Animal Health and Production, 2026)

Establishment of Method Validation Criteria and Internal Quality Control System for Measurement of Glucose in Accredited Laboratory - Swati Shalini; Amreen Fatima; Beulah Gowri; Harish Chander; Anup Anvikar; Varun Singh (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2026)

Neural bottlenecks: axon count, distribution, and conduction in the Manduca sexta neck connective - Leo Wood; Karrah Hayes; Varun Sharma; Eric Sun; Max Chen; Simon Sponberg (Journal of Comparative Physiology A, 2026)
Large flying insects precisely control fast maneuvers, a demanding task made more difficult by the limitation that all information between the brain and body is transmitted through a single transmission line, the neck connective. Despite this neuroanatomical structure constraining both the amount and timing of all information between the brain and body, little is known about how severe these bottlenecks are. We sought to understand this structure in the hawkmoth Manduca sexta by directly measuring axon count and conduction velocities in their neck connective, using a nanometer-scale complete map of the neck connective in concert with microelectrode array recordings from hundreds of neurons. We hypothesized that Manduca opts for a large spatial bottleneck, with comparatively few neurons in their neck connective compared to their brain size, but latency constraints of agile flight necessitate adaptations for increased conduction velocity compared to small insects. Manduca had 8,874 total neck connective axons, a number similar to fruit flies despite Manduca ’s order of magnitude greater body and brain size. Yet Manduca had far more giant axons, and the average conduction velocity of those axons exceeded 2 m/s, indicating a strong pressure on reducing neck connective latency. Both ascending and descending units were equally fast, and analyzing how velocity scales with diameter suggested adaptations beyond just axon size are increasing velocity. This data indicates Manduca ’s neck connective faces similar requirements to other species in terms of number of neurons, but more acute pressures for higher conduction velocity and reduced latency in the neck connective.

Dual-Modal Deep Learning with In-Domain Training and Attention for Infant Brain Myelination Prediction - Mamilla Sri Harshitha; Mythri G; Anju Thomas; Bibin Francis; Varun P. Gopi; Abhishek Sehrawat (Neuroinformatics, 2026)

Retraction Note: An ensemble learning–based experimental framework for smart landslide detection, monitoring, prediction, and warning in IoT-cloud environment - Aman Sharma; Rajni Mohana; Ashima Kukkar; Varun Chodha; Pranjal Bansal (Environmental Science and Pollution Research, 2026)

MSME sustainable performance in India's circular economy: Networks, innovation, and institutional enablers - Varun Sharma; Manisha Sharma (Journal of Cleaner Production, 2026)

Driving sustainable energy futures: Lessons from India and South Africa energy transition strategies - Varun Pratap Singh; Craig McGregor (Energy Policy, 2026)

Phytochemical profiling and chitosan nanoencapsulation of Betelvine (Piper betle L) leaf essential oil incorporated into hydrogel to combat multidrug-resistant β-lactamase and mecA-harbouring bacteria: In vitro and In vivo approach - Adrija Saha; N. Harshitha; Jyotibrata Mitra; Varun Shamanna; K.L. Ravikumar; Sunil S. More; Susweta Das Mitra (Biocatalysis and Agricultural Biotechnology, 2026)

Real-time PCR assay for the rapid and precise detection of the melon fly, Zeugodacus cucurbitae (Coquillett) (Diptera: Tephritidae) - Varun Arya; Srinivasa Narayana; Twinkle Sinha; Samantapudi Venkata Satyanarayana Raju (Phytoparasitica, 2026)

ANN-based broadband modelling of Fourier amplitude spectra through physics-based simulations: application to 2023 Elbistan earthquake - Varun Sharma; J. Dhanya; Maheshreddy Gade; Harsh Kumar Arya (Journal of Seismology, 2026)

Comprehensive genomic analysis of rabies virus in India reveals distinct lineages and evolutionary stability - Chakrakodi N. Varun; Shubhangi Chandel; Dhanya Keshava Kumar; Nayana Siddalingaiah; Surbhi Telang; Preeti Soundarya Bhalke; Shrikrishna Isloor; Vijaylakshmi Reddy; M. A. Ashwini; Anita Mahadevan; Reeta S. Mani (Virus Genes, 2026)

High Seropositivity for Helminths in Immunosuppressed Patients with Peripheral Eosinophilia - Abhishek Mewara; Nikita Sharma; Vignesh Pandiarajan; Sahajal Dhooria; Varun Dhir; Gaurav Prakash; Surinder Singh Rana; Ayush Vasisth; Surjit Singh; Ritesh Agarwal (Acta Parasitologica, 2026)

MRO-MCS observed cold spots during the Martian year 34 global dust storm - Anirban Mandal; Jagabandhu Panda; Nirvan Abhilash; Bijay Kumar Guha; Varun Sheel (Icarus, 2026)

Toxicity of Semaglutide upon sub chronic administration in Rabbits - Chandrashekara Vishwanath; Kumar Krishnachari; Gowrav Perdur Adiga; Manohar Madhavdeshmukh; Akanksh Das; Zabiullah Alandur Jamal; Prabhakar Bhoite; Kalaiselvan Ponnusamy; Mohan Krishnappa; Varun Ahuja; Manoj Kumar Pananchukunnath; Anil Kunhihitlu; et al. (Toxicological Research, 2026)

Depleting retinoic acid synthesis in the nucleus accumbens shell produces a protective phenotype for emotional reactivity and drug-taking in rats - Yorkiris Mármol Contreras; Nolan M. Dvorak; Cynthia M. Tapia; Roxana Zaman; Jyothika Annareddy; Yves Balikosa; Nikita S. Gupta; Alex P. Rader; Tileena E. S. Vasquez; Shyny Koshy; Dingge Li; Varun K. Balaji; et al. (Psychopharmacology, 2026)

Nobiletin Modulates Transcriptomic and Metabolomic Alterations in Aβ42-Induced Primary Rat Astrocytes: Implications for Alzheimer’s Disease - Sanjay; Varun Jaiswal; Miey Park; Hae-Jeung Lee (Molecular Neurobiology, 2026)

Boundary Layer Meteorology in Elysium Planitia, Mars During a Global Dust Storm - Insights from a Dust Reservoir - Varun Sheel; Rishitosh Kumar Sinha; Tirtha Jyoti Kalita (Journal of the Indian Society of Remote Sensing, 2026)

Effect of Monochromatic Light Spectra on Morphophysiological and Biochemical Properties of Chrysanthemum morifolium cv. Zembla Under Different Temperature Regimes - Panchal Sangmesh; Mam Chand Singh; Lekshmy Sathee; Gunjeet Kumar; Namita; Amrender Kumar; Ediga Amala; B. H. Varun; Neeraj Singh Negi (Journal of Plant Growth Regulation, 2025)

Species sensitivity distribution modeling for ecotoxicity prediction of industrial chemicals - Kabiruddin Khan; Nyssa Tucker; Holli-Joi Martin; Varun Gopalakrishnan Nair; Asmaa Ali; Ghada Tagorti; Barry Hardy (Science of The Total Environment, 2025)

Phytochemical analysis and toxicity evaluation of Uraria picta (Jacq.) Desv. ex DC. through In Vitro and In Vivo approaches - Richa Yadav; Varun Gorki; Shabnam Thakur; Shubhangi Kansal; Sofia Gupta; Birendra Kumar; Upninder Kaur; Bikash Medhi; Rakesh Sehgal (Next Research, 2025)

Insights into Pinus species: phytochemistry, pharmacology and industrial potential of Indian Pinus species - Rohit Sharma; Rahul Sharma; Varun Thakur; Aditi Randhawa; Rajneesh Kumar; Bhupender Dutt; Ashun Chaudhary; Sunil Kumar (Phytochemistry Reviews, 2025)

Emerging contaminants in healthcare effluents: antibiotic resistance and virulence factor dissemination - Jaya Malik; Zayera Naushad; Shilpy Singh; Dharmsheel Shrivastav; Ved Vrat Verma; Manoj Kumar Mishra; Ravi Kant Pal; Varun Kumar Sharma (Folia Microbiologica, 2025)

A new framework and classification scheme to indicate best-fit agroforestry systems: a locally adapted approach in the western coast of India - Harshavardhan Sarita Krishnarao Deshmukh; Minalkumar B. Tandel; Manmohan J. Dobriyal; Rajesh Gunaga; Ripu Kunwar; Narender Singh Thakur; Santoshkumar A. Huse; Ram Prasad Acharya; K. R. Ramesh; Shailesh S. Harne; Vishal B. Shambharkar; Ram J. Mevada; et al. (Agroforestry Systems, 2025)

The environmental threat of macrolide resistance: mechanisms, dissemination pathways, and urgent mitigation strategies - Arpana Devi; Varun Kumar Sharma; Dharmsheel Shrivastav; Shilpy Singh (Environmental Monitoring and Assessment, 2025)

Multi-hazard microzonation of Joshimath, India, considering seismic and landslide hazards - Varun Kumar; Vibhav Kumar Gupta; Rajib Sarkar; Sanjit Kumar Pal (Journal of Earth System Science, 2025)

Energy, exergy, environmental and sustainability assessment of renewable n-octanol biofuel on a compression ignition engine - Kuber Singh Mehra; Varun Goel (Biomass and Bioenergy, 2025)

Exploring the Therapeutic Landscape of Probiotics in Enteric and Respiratory Viral Infections - Yashpal Singh Malik; Aakriti Pathania; Ujjwal Kumar De; Manu M.; Harsh Panwar; Jaspreet Kaur; Adarsh Mishra; Naveen Kumar; Souvik Ghosh; Varun Kumar Sarkar; Sakshi (Probiotics and Antimicrobial Proteins, 2025)

An investigative assessment of the stability of natural and road-cut rock slopes using empirical rock mass classification systems and numerical methods: case study of NH-07 from the Garhwal Himalayas, India - Nalini Das; Subhamoy Ghosh; Rajendra Kumar Rawat; Barun Bedanta Sahoo; Varun Shastri; Sumana Murmu (Natural Hazards, 2025)

Utility of Urinary Biomarkers for Diagnosis of Acute Kidney Injury (AKI) in COVID-19 - Tanvir Samra; Vinod Kumar; Raja Ramachandran; Varun Mahajan; Naveen B. Naik; Goverdhan Dutt Puri; Ashish Bhalla; Arnab Pal; Ravi Dixit; Prabhjot Kaur (Indian Journal of Clinical Biochemistry, 2025)

Altitude-driven changes in carbon storage, soil properties, and leaf nutritional value of Quercus semecarpifolia in the northwestern Himalayas - Rishav Sharma; Rohit Bishist; Rajesh Kaushal; Prem Prakash; Krishan Lal Gautam; Ashok Kumar; Harish Sharma; Varun Thakur; Munesh Kumar (Environmental Sustainability, 2025)

LP-53 Evaluation of the Mutagenic Potential of 1-Cyclopentyl-4-Nitrosopiperazine Nitrosamine in Human Lymphoblastoid TK6and CHO-K1 Cells - M. Shameer P; T. Pradeep; M. Rajini; A. Mariappan; S. Sandhya; G. Kulavardhan; M. Sumithra; R. Harika; A. Varun; K. Mohan; V. Deepa (Toxicology Letters, 2025)

Antimalarial efficacy of Sonchus brachyotus D.C (Asteraceace) used in traditional herbal medicine - Neha Sylvia Walter; Varun Gorki; Upma Bagai (South African Journal of Botany, 2025)

Integrated optical and SAR data analysis for the monsoonal flood hazard mapping in the Tawi Basin Northwest Himalaya - Ajay Kumar Taloor; Varun Khajuria; Savati Sharma; Gurnam Parsad; Shiwalika Sambyal; Girish Ch Kothyari; Meenakshi Sharma; Pankaj Mehta (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Relationship between gut microbiota and multiple sclerosis: A comprehensive bibliometric and visual analysis of global research trends and therapeutics - Anupam Bhattacharya; Kushagra Agarwal; Nirmal Kumar Ganguly; Varun Suroliya (Next Research, 2025)

A cumulative dietary pesticide exposure score based on produce consumption is associated with urinary pesticide biomarkers in a U.S. biomonitoring cohort - Alexis M. Temkin; Varun Subramaniam; Alexa Friedman; Elvira Fleury; Dayna de Montagnac; Chris Campbell; David Q. Andrews; Olga V. Naidenko (International Journal of Hygiene and Environmental Health, 2025)

Carbon dots: An emerging food analysis nanoprobes for detection of contaminants - Hemant Singh; Saima; Varun Aggarwal; Ankit Kachore; Ekta Bala; Rakesh Kumar; Rohit K. Sharma; Praveen Kumar Verma (Food Chemistry, 2025)

Druggability assessments of small peptides as protein–protein interaction inhibitors targeting EED-EZH2 binding within the Polycomb Repressive Complex 2 (PRC2), an epigenetic regulator - Varun Thachan Kundil; Sharanya C. Suresh; Sreeja Chellappan; Anupama Kizhakkepurayil; Soorej Muhammad Basheer; Arun Kumar Gangadharan (Molecular Diversity, 2025)

An Updated Perspective on Skin Disease Therapy: From Conventional Methods to Nanocarrier Innovations - Riya Shivgotra; Bindu Soni; Parminder Kaur; Anshuka Sharma; Varun Singh; Nitin Partap; Hossamaldeen Bakrey; Subheet Kumar Jain (AAPS PharmSciTech, 2025)

Phenotypic discrimination and characterization of microbial populations in enhanced biological phosphorus removal using single-cell raman spectroscopy-based methods - Jiayu Bi; Ricardo Marques; Dongqi Wang; Lu Qin; Kylie Close; Guangyu Li; Zijian Leo Wang; Nicholas B. Tooker; Varun Srinivasan; Annalisa Onnis-Hayden; Adrian Oehmen; April Z. Gu (Water Research, 2025)

Unravelling sustainable impediments in E-waste supply chain management: A Fuzzy-WINGS decision approach - Varun Kumar; Om Ji Shukla (Journal of Environmental Management, 2025)

Muroid rodents from the Lower Siwalik deposits near Ramnagar (Jammu and Kashmir), India: Biostratigraphic implication - Varun Parmar; Rigzin Norboo; Deepak Singh Kshetrimayum; Rahul Magotra (Geobios, 2025)

Unveiling next-generation biodiesel Technologies: Techno-Economic and energy breakthroughs for sustainable production - Kuber Singh Mehra; Varun Goel (Biomass and Bioenergy, 2025)

A Spatiotemporal Study on Glacial Lake Dynamics and Its Response to Changing Climate in the Eastern District of Himachal Pradesh - Divya Singh; Varun Joshi (International Journal of Environmental Research, 2025)

Metagenomic analysis revealed community-level metabolic differences between full-scale EBPR and S2EBPR systems - Guangyu Li; Varun Srinivasan; Nicholas B. Tooker; Dongqi Wang; Annalisa Onnis-Hayden; Charles Bott; Paul Dombrowski; Ameet Pinto; April Z. Gu (Water Research, 2025)

Late Quaternary fluvio-aeolian interactions and possible aridification in west-central India: Implications for prehistoric human adaptations in the Central Tapi Valley - Sourav Mukhopadhyay; Pratik Pandey; Prabhin Sukumaran; Binita Phartiyal; Swati Verma; Varun Vyas; Navashni Naidoo; Avantika Binani; Jessica L. Conroy; Parth R. Chauhan (Quaternary International, 2025)

Data-driven techniques in rainfall forecasting using CMIP6 simulation outputs and ground-observed data - Varun Dubey; Vikas Kumar Vidyarthi (Acta Geophysica, 2025)

Land use change analysis and prediction of urban growth using multi-layer perceptron neural network Markov chain model in Faridabad- A data-scarce region of Northwestern India - Sunil Kumar; Kousik Midya; Swagata Ghosh; Pradeep Kumar; Varun Narayan Mishra (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Spatio-temporal Variations and Forecast of PM2.5 concentration around selected Satellite Cities of Delhi, India using ARIMA model - Vipasha Sharma; Swagata Ghosh; Varun Narayan Mishra; Pradeep Kumar (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Polyethylene terephthalate (PET) waste in electrochemical applications - Varun Donnakatte Neelalochana; Paolo Scardi; Narges Ataollahi (Journal of Environmental Chemical Engineering, 2025)

Omega-3 Fatty Acids and Risk of Ischemic Stroke in REGARDS - Zsuzsanna Ament; Amit Patki; Varun M. Bhave; Naruchorn Kijpaisalratana; Alana C. Jones; Catharine A. Couch; Robert J. Stanton; Pamela M. Rist; Mary Cushman; Suzanne E. Judd; D. Leann Long; M. Ryan Irvin; et al. (Translational Stroke Research, 2025)

Soil Phosphorus Fractions and Balance in Response to Integrated Phosphorus Management in an Acid Alfisol of North West Himalayas - Dhanbir Singh; Rewangini Ranjha; Sanjay K. Sharma; Prakriti Kaistha; Varun Parmar (Journal of Soil Science and Plant Nutrition, 2025)

Ground shaking hazard assessment in Jharkhand state, India, using deterministic approach - Varun Kumar (Acta Geophysica, 2025)

Human endothelial colony forming cells (ECFCs) require endothelial protein C receptor (EPCR) for cell cycle progression and angiogenic activity - Sarah E. J. Chambers; Jasenka Guduric-Fuchs; Edoardo Pedrini; Pietro M. Bertelli; Chutima Charoensuk; Elisa Peixoto; Varun Pathak; Hamza I. Alhamdan; Ruoxiao Xie; Anna Krasnodembskaya; Judith Lechner; Alan W. Stitt; et al. (Angiogenesis, 2025)
Vascular repair and regeneration are critical for tissue homeostasis. Endothelial colony forming cells (ECFCs) are vessel-resident progenitors with vasoreparative capacity and they offer an important avenue for allogeneic cytotherapy to achieve perfusion of ischemic tissues. Endothelial Protein C Receptor (EPCR) has been proposed as a marker for vascular endothelial stem cells, but its precise role in ECFC biology remains unknown. The current study has investigated the biological relevance of EPCR in ECFC function. Our data show that over 95% of ECFCs exhibit high EPCR expression. These levels surpassing CD34 and CD157, positions EPCR as a new robust ECFC immunophenotypic marker, alongside established markers CD31 and CD105. Functionally, depleting EPCR expression in ECFCs significantly diminished angiogenic activity, including proliferation, migration and tube formation. This knockdown also altered normal ECFC barrier function. Transcriptomic analysis indicated that knockdown of EPCR led to enrichment of gene signatures for cell cycle, TGF beta, and focal adhesion kinases. G1 cell cycle arrest was confirmed in ECFCs with depleted EPCR. Mechanistically, EPCR knockdown led to increased release of TGFβ2 and SMAD2/3 activation, coupled with increased p21, decreased pFAK, and increased transgelin. Additionally, we showed that quiescent ECFCs showed significantly lower EPCR expression when compared to proliferating ECFCs. In agreement with this, cell sorting experiments demonstrated that ECFCs with the highest EPCR expression exhibited the highest clonogenic capacity. In summary, our findings highlight that EPCR expression in ECFCs is critical for their angiogenic activity, by modulating cell cycle progression. Graphical abstract

Characterization of azo dye-degrading Tistrella mobilis isolated from industrial effluents: a molecular perspective - Ufondu Maryann Afoma; Jaya Malik; Shilpy Singh; Abhishek Kumar Mishra; Lomas Kumar Tomar; Aditi Tomar; Ved Vrat Verma; Manoj Kumar Mishra; Varun Kumar Sharma (Biologia, 2025)

Assessing Gaddi dogs as a non-lethal predator deterrent in the north-western Himalayan transhumant pastoralism - Ankaj Thakur; Rakesh Thakur; Aadarsh Kumar; Brij Vanita; Varun Sankhyan; Shivani Katoch (Journal of Veterinary Behavior, 2025)

Changing tropospheric NO2 dynamics across Indian air pollution hotspots - Akash Biswal; Varun Katoch; Tanbir Singh; Khaiwal Ravindra; Vikas Singh; Suman Mor (Environmental Pollution, 2025)

Seasonal patterns of air pollution in Delhi: interplay between meteorological conditions and emission sources - Najib Ansari; Preeti Kumari; Rahul Kumar; Pavan Kumar; Aquib Shamshad; Saddam Hossain; Ashutosh Sharma; Yogeshwar Singh; Maya Kumari; Varun Narayan Mishra; Rukhsana; Akram Javed (Environmental Geochemistry and Health, 2025)

Scratching beneath the surface: Using Ground-Penetrating Radar to disentangle pronival ramparts, embryonic rock glaciers and moraines (Gardetta Plateau, Southwestern Alps) - Adriano Ribolini; Emanuele Forte; Varun Khajuria; Renato R. Colucci; Luca Paro; Mauro Guglielmin (Geomorphology, 2025)

Web crippling strength of GI based cold- formed steel under high temperature: experimental and analytical modeling - Varun Sabu Sam; N. Anand; Deon Joseph; Siew Choo Chin (Innovative Infrastructure Solutions, 2025)

Alzheimer’s Disease and Circulatory Imbalance of Toxic Heavy Metals: A Systematic Review and Meta-analysis of Clinical Studies - Alireza Kooshki; Reyhane Farmani; Omid Mehrpour; Ali Naghizadeh; Alireza Amirabadizadeh; Sepide Kavoosi; Varun Vohra; Samaneh Nakhaee (Biological Trace Element Research, 2025)

Influences of anaerobic treatment on chemical oxygen demand removal behavior of tannery wastewater - Venkatesh Rathinavelu; Viyat Varun Upadhyay; Rakesh Kumar; Vinayagam Mohanavel; Nagabhooshanam Nagarajan; Dhaval Rabadiya; Manzoore Elahi Mohammed Soudagar; Sami Al Obaid; Saleh Hussein Salmen (Environmental Monitoring and Assessment, 2025)

Designing potential long-term vaccine targets against emerging variants of SARS-CoV-2 using an immunoinformatics approach - Aditi Nag; Pratika Varun (Next Research, 2025)

Spatiotemporal dynamics of rice cultivation in India - Netrananda Sahu; Ravi Kesharwani; Pritiranjan Das; Anil Kumar; Ayush Varun; Atul Saini; Suraj Kumar Mallick; Martand Mani Mishra (Tropical Ecology, 2025)

Geoinformatics based evaluation of heat mitigation strategies through urban green spaces in a rapidly growing city of India: implications for urban resilience - Khushbu Joshi; Maya Kumari; Varun Narayan Mishra; Rajendra Prasad; Mohamed Zhran (Theoretical and Applied Climatology, 2025)

Conformational Transitions in EGFR Protein Tyrosine Kinase Domain and Their Modulation by Mutants - Eshrat Shaikh; Varun Talati; Deepanshu Garg; Ashay Baruah; Priyanka Joshi; Virupaksha Bastikar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2025)

Landslides and debris flow triggered by the July 2024 extreme rainstorm in the Chooralmala watershed in Wayanad, India - Sreevalsa Kolathayar; Varun Menon; Priyajit Kundu (Landslides, 2025)

Gefitinib as an antimalarial: unveiling its therapeutic potential - Varun Gorki; Neha Sylvia Walter; Monika Chauhan; Neelima Dhingra; Upma Bagai; Sukhbir Kaur (Inflammopharmacology, 2025)

A transfer learning-based ground motion model for Western Himalayas - Romani Choudhary; Varun Sharma; Jaya Dhanya; Maheshreddy Gade (Acta Geophysica, 2025)

People with disabilities and transit use: Findings from nationwide data in India - G.M. Hridya; Agnivesh Pani; Varun Varghese; Gaurav Tripathi; Avinash Unnikrishnan (Transportation Research Part D: Transport and Environment, 2025)

Data-driven analysis of property-performance correlations in dual functional materials for CO2 capture and utilization - Lukas C. Buelens; Louis Van de Voorde; Varun J. Singh; Michiel W.F. Van Cauwelaert; Hilde Poelman; Kevin M. Van Geem; Vladimir V. Galvita (Chemical Engineering Journal, 2025)

Toxicological profile of Acovenoside A as an active pharmaceutical ingredient – prediction of missing key toxicological endpoints using in silico toxicology methodology - Kamil Jurowski; Łukasz Niżnik; Adrian Frydrych; Damian Kobylarz; Maciej Noga; Alicja Krośniak; Oktawia Fijałkowska; Agnieszka Świdniak; Varun Ahuja (Chemico-Biological Interactions, 2025)

ANN-Based Ground Motion and Physics-Based Broadband Models for Vertical Spectra - Varun Sharma; Harsh Kumar Arya Author; Maheshreddy Gade; J. Dhanya (Pure and Applied Geophysics, 2025)

Influence of Bemisia tabaci-Induced Plant Volatiles on the Host-Choice Behavior of Tuta absoluta - Subhash Shivaramu; Kamala Jayanthi Pagadala Damodaram; Anuj Bhatnagar; Kailash Chandra Naga; Varun Yennurukadirenahalli Byregowda; Aarti Bairwa; Sanjeev Sharma; Rajesh Kumar Singh; Brajesh Singh; Vivek Kempraj (Journal of Chemical Ecology, 2025)

A spatially explicit assessment of factors shaping attitudes toward African elephant conservation - Sarah L. Carroll; Susanne M. Vogel; Purity Nititi Taek; Clevers Tumuti; Divya Vasudev; Varun R. Goswami; Jake Wall; Stephen Mwiu; Robin S. Reid; Jonathan Salerno (Conservation Biology, 2025)
Conservation plans that explicitly account for the social landscape where people and wildlife co‐occur can yield more effective and equitable conservation practices and outcomes. Yet, social data remain underutilized, often because social data are treated as aspatial or are analyzed with approaches that do not quantify uncertainty or address bias in self‐reported data. We conducted a survey (questionnaires) of 177 households in a multiuse landscape in the Kenya–Tanzania borderlands. In a mixed‐methods approach, we used Bayesian hierarchical models to quantify and map local attitudes toward African elephant ( Loxodonta africana ) conservation while accounting for response bias and then combined inference from attitude models with thematic analysis of open‐ended responses and cointerpretation of results with local communities to gain deeper understanding of what explains attitudes of people living with wildlife. Model estimates showed that believing elephants have sociocultural value increased the probability of respondents holding positive attitudes toward elephant conservation in general (mean increase = 0.31 [95% credible interval, CrI, 0.02–0.67]), but experiencing negative impacts from any wildlife species lowered the probability of respondents holding a positive attitude toward local elephant conservation (mean decrease = −0.20 [95% CrI −0.42 to 0.03]). Qualitative data revealed that safety and well‐being concerns related to the perceived threats that elephants pose to human lives and livelihoods, and limited incentives to support conservation on community and private lands lowered positive local attitude probabilities and contributed to negative perceptions of human–elephant coexistence. Our spatially explicit modeling approach revealed fine‐scale variation in drivers of conservation attitudes that can inform targeted conservation planning. Our results suggest that approaches focused on sustaining existing sociocultural values and relationships with wildlife, investing in well‐being, and implementing species‐agnostic approaches to wildlife impact mitigation could improve conservation outcomes in shared landscapes.

Novel extraction technique: quantification of major phytoconstituents of arjuna in infused edible oil - Rajesh Kumar Verma; Neelam Pal; Sujeet Gupta; Varun Kumar Singh; Priyanka Gupta; Sunanda Handoo; Charan Singh Rana (Natural Product Research, 2025)

Strontium minerals as critical raw materials — Market dynamics, processing techniques, and future challenges - Diego Mesa; Varun Gowda; Francisco Ortega; Kanishk Bhadani; Noemi Ariza-Rodríguez; Gauti Asbjörnsson; Pablo R. Brito-Parada (Minerals Engineering, 2025)

Integrating one health strategies for rabies control: Insights from Jackal-mediated human rabies in Northeast India - Jyoti B. Dutta; MA Ashwini; Ditul Barman; Pranab Das; Raktim Tamuli; K. Dhanya; CN Varun; Shubhangi Chandel; P. Soundarya; Shrikrishna Isloor; Reeta S. Mani (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Quantifying urban flood extent using satellite imagery and machine learning - Rebecca W. Composto; Mirela G. Tulbure; Varun Tiwari; Mollie D. Gaines; Júlio Caineta (Natural Hazards, 2025)

Defaunation Increases Clustering and Fine‐Scale Spatial Genetic Structure in a Small‐Seeded Palm Despite Remaining Small‐Bodied Frugivores - Therese Lamperty; Zoe Diaz‐Martin; Varun Swamy; Jordan Karubian; Juanita Choo; Amy E. Dunham (Molecular Ecology, 2025)
Anthropogenic pressures such as hunting are increasingly driving the localised functional extinctions of large‐ and medium‐sized wildlife in tropical forests, a phenomenon broadly termed ‘defaunation’. Concurrently in these areas, smaller‐bodied species benefit from factors such as competitive release and increase in numbers. This transformation of the wildlife community can impact species interactions and ecosystem services such as seed dispersal and seed‐mediated geneflow with far‐reaching consequences. Evidence for negative genetic effects following defaunation is well‐documented in large‐seeded plants that require large frugivores for long‐distance seed dispersal. However, how defaunation affects plants with small or medium‐small seeds ( Euterpe precatoria in three sites with different defaunation levels. Results indicate that defaunation is associated with higher fine‐scale spatial genetic structure among seedlings and increased spatial clustering within seedling cohorts and between seedlings and conspecific adults, as well as a reduction in nearest‐neighbour distances between seedlings and conspecific adults. There were no clear effects on inbreeding or genetic diversity. However, we caution these trends may indicate that defaunation reduces seed dispersal services for species previously presumed to be robust to deleterious effects of losing large frugivores by virtue of having smaller seeds and broad suites of dispersal agents, and negative downstream effects on genetic diversity could occur.

Diagnosis, taxonomic keys, DNA barcoding and molecular phylogeny of economically important fruit fly species (Diptera;Tephritidae) - Vishrutha Chandrashekhar; Varun Arya; Karamakodu Jacob David; Srinivasa Narayana (International Journal of Tropical Insect Science, 2024)

Analysis of downstream targets of PAX6 and LHX2, fundamental regulators of the developing mammalian neocortex - Mansi Srivastava; Varun Suresh; Shubha Tole (Journal of Biosciences, 2024)

Seismic hazard assessment of Faizabad region of Uttar Pradesh, India, utilizing deterministic and probabilistic approaches - Varun Kumar; Prosanta Kumar Khan; Rajib Sarkar; Sanjit Kumar Pal (Journal of Earth System Science, 2024)

Spatially explicit simulation and forecasting of urban growth using weights of evidence based cellular automata model in a millennium city of India - Pankaj Kumar Yadav; Varun Narayan Mishra; Maya Kumari; Akshay Kumar; Pradeep Kumar; Rajeev Bhatla (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Molecular evidence of novel Begomoviruses and associated Betasatellite complexes linked to Papaya Leaf Curl Disease in Indian Provinces - Priyanka; Priyanka Varun; Yusuf Akhter; Sangeeta Saxena (Ecological Genetics and Genomics, 2024)

Single-cell transcriptomics: a new frontier in plant biotechnology research - Shilpy Singh; Afsana Praveen; Namrata Dudha; Varun Kumar Sharma; Pooja Bhadrecha (Plant Cell Reports, 2024)

Early-stage Development of the CoRISMA Mechanical Circulatory Support (CMCS) System for Heart Failure Therapy - Gretel Monreal; Steven C. Koenig; James F. Kelley; Jessica J. Illg; Daniel Tamez; Mark S. Kelley; Varun Yetukuri; Daisy P. Cross; Michael E. Theran; Mark S. Slaughter (Cardiovascular Engineering and Technology, 2024)

Production, purification and characterization of phytase from Pichia kudriavevii FSMP-Y17and its application in layers feed - Ritu Sharma; Arpana Mittal; Varun Gupta; Neeraj K. Aggarwal (Brazilian Journal of Microbiology, 2024)

Enhanced Crop Yield Forecasting Using Deep Reinforcement Learning and Multi-source Remote Sensing Data - Yogita Rahulsing Chavan; Brinthakumari Swamikan; Megha Varun Gupta; Sunil Bobade; Anu Malhan (Remote Sensing in Earth Systems Sciences, 2024)

Multifaceted dimensions of greywater recycling in advancing sustainable development goals: a comprehensive review - Om Prakash; Purusottam Tripathy; Aditi Zade; Abhishek Sharma; Charu Juneja; Isha Hiwrale; Varun Shukla; Krishnamurthi Kannan; Sukdeb Pal (Environment, Development and Sustainability, 2024)

Distinct microdiversity of phosphate accumulating organisms (PAOs) between side-stream and conventional enhanced biological phosphorus removal (EBPR) systems with performance implications - Guangyu Li; Varun Srinivasan; Nicholas B. Tooker; Dongqi Wang; Yuan Yan; Annalisa Onnis-Hayden; April Z. Gu (Water Research, 2024)

Molecular evidence of internal carbon-driven partial denitrification in a mainstream pilot A-B system coupled with side-stream EBPR treating municipal wastewater - Da Kang; Yuan Yan; IL Han; Jangho Lee; Kester McCullough; Guangyu Li; Zijian Leo Wang; Peisheng He; Dongqi Wang; Stephanie Klaus; Ping Zheng; Varun Srinivasan; et al. (Water Research, 2024)

Managing transit-oriented development: A comparative analysis of expert groups and multi-criteria decision making methods - Reza Abdullah; Blessy David Xavier; Hyewon Namgung; Varun Varghese; Akimasa Fujiwara (Sustainable Cities and Society, 2024)

Organic municipal solid waste derived hydrogen production through supercritical water gasification process configured with K2CO3/SiO2: Performance study - Manzoore Elahi M. Soudagar; Viyat Varun Upadhyay; N Naga Bhooshanam; Ravindra Pratap Singh; Dhaval Rabadiya; R. Venkatesh; Vinayagam Mohanavel; Majed A. Alotaibi; A.H. Seikh (Biomass and Bioenergy, 2024)

Correction to: Smallholder farmer resilience to extreme weather events in a global food value chain - William J. Thompson; Varun Varma; Jonas Joerin; Solhanlle Bonilla-Duarte; Daniel P. Bebber; Wilma Blaser-Hart; Birgit Kopainsky; Leonhard Späth; Bianca Curcio; Johan Six; Pius Krütli (Climatic Change, 2024)

A comprehensive assessment of IAQ role in ensuring environment quality and health in schools and plan for future school environment: a systematic review - Venu Shree; Harsimran Kaur; Kuber Singh Mehra; Varun Goel; Himanshu Goel (Air Quality, Atmosphere & Health, 2024)

Considerations for using tree-based machine learning to assess causation between demographic and environmental risk factors and health outcomes - Daniela Galatro; Alessia Di Nardo; Varun Pai; Rosario Trigo-Ferre; Melanie Jeffrey; Maria Jacome; Vincenzo Costanzo-Alvarez; Jason Bazylak; Cristina H. Amon (Environmental Science and Pollution Research, 2024)

Spatial correlation analysis for ANN generated physics-based broadband response spectra: A case study for 2023 Turkey events - Varun Sharma; J Dhanya; Maheshreddy Gade; Romani Choudhary (Journal of Earth System Science, 2024)

The short-term toxicity and metabolome of Benzene - Frank Faulhammer; Bennard van Ravenzwaay; A. Robert Schnatter; Martijn Rooseboom; Hennicke Kamp; Burkhard Flick; Varun Giri; Saskia Sperber; Larry G. Higgins; Michael G. Penman; Neslihan Aygun Kocabas (Toxicology Letters, 2024)

A state-of-art review on photovoltaic systems: Design, performance, and progress - Abhishek Saxena; Rajneesh Kumar; Atul A. Sagade; Desh Bandhu Singh; V.V. Tyagi; Erdem Cuce; Varun Goel (Process Safety and Environmental Protection, 2024)

Unveiling pollutants in Sonipat district, Haryana: Exploring seasonal, spatial and meteorological patterns - Diksha; Maya Kumari; Varun Narayan Mishra; Deepak Kumar; Pradeep Kumar; Hazem Ghassan Abdo (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Rainfall-runoff modelling using GIS based SCS-CN method in umiam catchment region, Meghalaya, India - Maya Kumari; Diksha; Pranjit Kalita; Varun Narayan Mishra; Arti Choudhary; Hazem Ghassan Abdo (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Re-examining the role of street network configuration on bicycle commuting using crowdsourced data - Varun Raturi; David Philip McArthur; Jinhyun Hong (Journal of Transport Geography, 2024)

Honeycomb polypore biomass-derived activated porous carbon nanosheets/graphite/nafion composite: Green and sensitive electrocatalyst for nanomolar detection of Hg2+ ions and water-splitting reactions - N. Hareesha; D.M. Soumya; Mounesh; J.G. Manjunatha; R.N. Rohit; P. Manikanta; D.N. Varun; N. Ataollahi; B.A. Thippeswamy; K. Pramoda; B.M. Nagaraja (Journal of Environmental Chemical Engineering, 2024)

Environmental Magnetic and Morphological Characteristics of Topsoils from the Coal Capital of India-Dhanbad - Mahesh Kapawar; Varun Kumar; Ravi Shankar; Venkateshwarlu Mamilla (Water, Air, & Soil Pollution, 2024)

Acetylglutamine Differentially Associated with First-Time Versus Recurrent Stroke - Naruchorn Kijpaisalratana; Zsuzsanna Ament; Amit Patki; Varun M. Bhave; Alana C. Jones; Ana-Lucia Garcia Guarniz; Catharine A. Couch; Mary Cushman; D. Leann Long; M. Ryan Irvin; W. Taylor Kimberly (Translational Stroke Research, 2024)

Flexural behavior of cold-formed mild steel beams with web holes exposed to high temperature: analytical and experimental investigation - Varun Sabu Sam; N. Anand; M. Z. Naser (Innovative Infrastructure Solutions, 2024)

Changing the default meal option at university events to reduce harmful environmental impacts: Six randomized controlled trials - Angela W. Zhang; Christopher Wharton; Sara Cloonan; Renate Boronowsky; Varun Magesh; Ilana Braverman; Alejandra Marquez; Heather Leidy; May C. Wang; David A. Cleveland; Jennifer Jay; Chad Stecher (Appetite, 2024)

The impact of a low traffic neighbourhood intervention on urban noise measured with low-cost sensors in Oxford, UK - Felix C.P. Leach; Jingyuan Yang; Varun Shankar; Stuart Cole; Katie Parnell; Mani Entezami; Suzanne E. Bartington (Transportation Research Part D: Transport and Environment, 2024)

Impact of climate and weather extremes on soybean and wheat yield using machine learning approach - Mamta Kumari; Abhishek Chakraborty; Vishnubhotla Chakravarathi; Varun Pandey; Parth Sarathi Roy (Stochastic Environmental Research and Risk Assessment, 2024)

Synthesis, characterization, and study of photocatalytic degradation of aniline blue dye using copper oxide nanoparticles prepared by Santa Maria feverfew leaf extract - Upendra Kumar Mishra; Vishal Singh Chandel; Avaneesh Kumar Yadav; Abhishek Kumar Gautam; Aditya Dev Anand; Juli Varun; Amit Kumar Rai; Satyendra Pratap Singh (Nanotechnology for Environmental Engineering, 2024)

Clinical and Genomic Perspective of SARS CoV-2 Infection in Liver Disease Patients: A Single-Centre Retrospective Study - Reshu Agarwal; Arjun Bhugra; Pramod Gautam; Varun Suroliya; Ruchita Chhabra; Amit Pandey; Prince Garg; Pooja Rao; Rosmy Babu; Guresh Kumar; Chhagan Bihari; Debajyoti Bhattacharyya; et al. (Current Microbiology, 2024)

Development of a loop-mediated isothermal amplification assay for accurate and rapid identification of Spodoptera frugiperda in maize from India - Twinkle Sinha; Srinivasa Narayana; Varun Arya; Aravindaram Kandan; Samantapudi Venkata Satyanarayana Raju; Ipsita Samal (Cereal Research Communications, 2024)

Impact of climate change on future flood susceptibility projections under shared socioeconomic pathway scenarios in South Asia using artificial intelligence algorithms - Saeid Janizadeh; Dongkyun Kim; Changhyun Jun; Sayed M. Bateni; Manish Pandey; Varun Narayan Mishra (Journal of Environmental Management, 2024)

Five Himalayan weeds as potential bioresources for bioactive agents: toxic compounds to valuable scaffolds - Ekta Bala; Varun Aggarwal; Pawan Kumar; Rohit Sharma; Saima; Manickam Selvaraj; Mohammed A. Assiri; Praveen Kumar Verma (Phytochemistry Reviews, 2024)

Variation of ambient air pollutants and their impacts on Kanpur city, India, during 2016–2020 - Varun Yadav; Rajiv Ganguly (Journal of Earth System Science, 2024)

Impact of urban growth in Delhi and It's Peri-urban environment on urban heat exposure - Suraj Kumar Mallick; Netrananda Sahu; Pritiranjan Das; Biswajit Maity; Ayush Varun; Anil Kumar; Ravi Keswarwani; Atul Saini; Somnath Rudra (Urban Climate, 2024)

Data processing of visible emission line coronagraph onboard ADITYA-L1 - Muthu Priyal; Jagdev Singh; B. Raghavendra Prasad; Chavali Sumana; Varun Kumar; Shalabh Mishra; S.N. Venkata; G. Sindhuja; K. Sasikumar Raja; Amit Kumar; Sanal krishnan; Bhavana S. Hegde; et al. (Advances in Space Research, 2024)

Correction to: Bioprospecting the gut microbiome of major weevil pests of banana - Shriniketan PuranikMeenal; Meenal Vyas; Varun Yennurukadirenahalli Byregowda; Geethashree Kuntayyanapalya Govindaraju; Krishnarao Gandham; Kamala Jayanthi Pagadala Damodaram (International Journal of Tropical Insect Science, 2024)

Categorisation by Leveraging CNNs and Remote Sensing Satellite Imagery for Crop Analysis in Arid Environments - Anu Malhan; Yogita Rahulsing Chavan; Brinthakumari Swamikan; Megha Varun Gupta; Sunil Bobade (Remote Sensing in Earth Systems Sciences, 2024)

Accelerative Solid-State Oxidation Behaviour of Amorphous and Partially Crystalline Venetoclax - Jesús Alberto Afonso Urich; Viktoria Marko; Katharina Boehm; Bernd Werner; Klaus Zangger; Isha Saraf; Amrit Paudel; Varun Kushwah (AAPS PharmSciTech, 2024)

Bioprospecting the gut microbiome of major weevil pests of banana - Shriniketan Puranik; Meenal Vyas; Varun Yennurukadirenahalli Byregowda; Geethashree Kuntayyanapalya Govindaraju; Krishnarao Gandham; Kamala Jayanthi Pagadala Damodaram (International Journal of Tropical Insect Science, 2024)

Phenylalanine encapsulation into an amphiphilic carboxymethyl cellulose-derivative enhanced plant uptake and metabolism efficiency - Varun Kumar; Stalin Nadarajan; Anita Kumari; Yael Cohen; Tal Klingbel; Einat Bar; Efraim Lewinsohn; Yigal Elad; Elena Poverenov; Michal Oren-Shamir (Postharvest Biology and Technology, 2024)

Deciphering the seasonal dynamics of microplastic morphotypes and associated co-contaminants along the northwest coast of India - Ankita C. Maurya; Amrik Bhattacharya; Varun Vij; Sunil K. Khare (Chemosphere, 2024)

Benzalkonium chloride and polyhexanide disinfectant (F10 SC) requires off-label use for environmental disinfection to be effective against Nannizziopsis guarroi - Varun Seth; Laura Adamovicz; Krista A Keller (Journal of Exotic Pet Medicine, 2024)

Facets of cost-benefit analysis of greywater recycling system in the framework of sustainable water security - Purusottam Tripathy; Om Prakash; Abhishek Sharma; Charu Juneja; Isha Hiwrale; Varun Shukla; Sukdeb Pal (Journal of Cleaner Production, 2024)

Rock mass permeability evolution during triaxial shearing based on three-dimensional distinct element model (3DEC) simulation - A.G. Corkum; L.J. Lorig; V. Varun (Computers and Geotechnics, 2024)

Overexpression of the chickpea Metallothionein 1 (MT1) gene enhances drought tolerance in mustard (Brassica juncea L.) - Swati Lal; Varun Kumar; Uma Gupta; Sushma; Pramod Arvind Shirke; Indraneel Sanyal (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Revisiting the role of Acinetobacter spp. in side-stream enhanced biological phosphorus removal (S2EBPR) systems - Yuan Yan; IL Han; Jangho Lee; Guangyu Li; Varun Srinivasan; Kester McCullough; Stephanie Klaus; Da Kang; Dongqi Wang; Peisheng He; Anand Patel; Charles Bott; et al. (Water Research, 2024)

Side-Stream Enhanced Biological Phosphorus Removal (S2EBPR) enables effective phosphorus removal in a pilot-scale A-B stage shortcut nitrogen removal system for mainstream municipal wastewater treatment - Dongqi Wang; Il Han; Kester McCullough; Stephanie Klaus; Jangho Lee; Varun Srinivasan; Guangyu Li; Zijian Leo Wang; Charles B. Bott; Jim McQuarrie; Beverley M. Stinson; Christine deBarbadillo; et al. (Water Research, 2024)

The short-term toxicity and metabolome of dicyclopentadiene - Bennard van Ravenzwaay; Neslihan Aygun Kocabas; Frank Faulhammer; Burkhard Flick; Varun Giri; Saskia Sperber; Michael G. Penman; Larry G. Higgins; Hennicke Kamp; Martijn Rooseboom (Toxicology Letters, 2024)

Taxonomy, biostratigraphy and paleoecology of non-marine ostracod fauna of the Maastrichtian intertrappean beds of the lower Narmada Basin, Malwa Plateau, India - Deepak Singh Kshetrimayum; Varun Parmar; Ranjit Singh Lourembam; Guntupalli V.R. Prasad (Palaeoworld, 2024)

Environmental sustainability and life cycle assessment of pilot scale application of coal combustion residue as structural fill in mechanically stabilized earth walls - Aali Pant; Lokesh Meena; Varun Pooja Desai (Journal of Cleaner Production, 2024)

Unveiling predictive insights for enhanced performance of PVDF-based nanogenerators via machine learning modeling - S. Varun; Akash M. Chandran; K.P. Minhaj; Vishnu Shaju; Lity Alen Varghese; Prasanna Kumar S. Mural (Chemical Engineering Journal, 2024)

The role of vision in sensory integration models for predicting motion perception and sickness - Varun Kotian; Tugrul Irmak; Daan Pool; Riender Happee (Experimental Brain Research, 2024)
Users of automated vehicles will engage in other activities and take their eyes off the road, making them prone to motion sickness. To resolve this, the current paper validates models predicting sickness in response to motion and visual conditions. We validate published models of vestibular and visual sensory integration that have been used for predicting motion sickness through sensory conflict. We use naturalistic driving data and laboratory motion (and vection) paradigms, such as sinusoidal translation and rotation at different frequencies, Earth-Vertical Axis Rotation, Off-Vertical Axis Rotation, Centrifugation, Somatogravic Illusion, and Pseudo-Coriolis, to evaluate different models for both motion perception and motion sickness. We investigate the effects of visual motion perception in terms of rotational velocity (visual flow) and verticality. According to our findings, the SVC I model, a 6DOF model based on the Subjective Vertical Conflict (SVC) theory, with visual rotational velocity input is effective at estimating motion sickness. However, it does not correctly replicate motion perception in paradigms such as roll-tilt perception during centrifuge, pitch perception during somatogravic illusion, and pitch perception during pseudo-Coriolis motions. On the other hand, the Multi-Sensory Observer Model (MSOM) accurately models motion perception in all considered paradigms, but does not effectively capture the frequency sensitivity of motion sickness, and the effects of vision on sickness. For both models (SVC I and MSOM), the visual perception of rotational velocity strongly affects sickness and perception. Visual verticality perception does not (yet) contribute to sickness prediction, and contributes to perception prediction only for the somatogravic illusion. In conclusion, the SVC I model with visual rotation velocity feedback is the current preferred option to design vehicle control algorithms for motion sickness reduction, while the MSOM best predicts perception. A unified model that jointly captures perception and motion sickness remains to be developed.

Molecular signatures of angiogenesis inhibitors: a single-embryo untargeted metabolomics approach in zebrafish - Pia Wilhelmi; Volker Haake; Franziska M. Zickgraf; Varun Giri; Philipp Ternes; Peter Driemert; Julia Nöth; Stefan Scholz; Marta Barenys; Burkhard Flick; Barbara Birk; Hennicke Kamp; et al. (Archives of Toxicology, 2024)
Angiogenesis is a key process in embryonic development, a disruption of this process can lead to severe developmental defects, such as limb malformations. The identification of molecular perturbations representative of antiangiogenesis in zebrafish embryo (ZFE) may guide the assessment of developmental toxicity from an endpoint- to a mechanism-based approach, thereby improving the extrapolation of findings to humans. Thus, the aim of the study was to discover molecular changes characteristic of antiangiogenesis and developmental toxicity. We exposed ZFEs to two antiangiogenic drugs (SU4312, sorafenib) and two developmental toxicants (methotrexate, rotenone) with putative antiangiogenic action. Molecular changes were measured by performing untargeted metabolomics in single embryos. The metabolome response was accompanied by the occurrence of morphological alterations. Two distinct metabolic effect patterns were observed. The first pattern comprised common effects of two specific angiogenesis inhibitors and the known teratogen methotrexate, strongly suggesting a shared mode of action of antiangiogenesis and developmental toxicity. The second pattern involved joint effects of methotrexate and rotenone, likely related to disturbances in energy metabolism. The metabolites of the first pattern, such as phosphatidylserines, pterines, retinol, or coenzyme Q precursors, represented potential links to antiangiogenesis and related developmental toxicity. The metabolic effect pattern can contribute to biomarker identification for a mechanism-based toxicological testing.

Age associated susceptibility to SARS-CoV-2 infection in the K18-hACE2 transgenic mouse model - Varun Dwivedi; Vinay Shivanna; Shalini Gautam; Jennifer Delgado; Amberlee Hicks; Marco Argonza; Reagan Meredith; Joanne Turner; Luis Martinez-Sobrido; Jordi B. Torrelles; Viraj Kulkarni (GeroScience, 2024)

Numerical analysis of extreme heat in Nagpur city using heat stress indices, all-cause mortality and local climate zone classification - Rajashree Kotharkar; Parikshit Dongarsane; Aveek Ghosh; Varun Kotharkar (Sustainable Cities and Society, 2024)

Automated in-season rice crop mapping using Sentinel time-series data and Google Earth Engine: A case study in climate-risk prone Bangladesh - Varun Tiwari; Mirela G. Tulbure; Júlio Caineta; Mollie D. Gaines; Vinicius Perin; Mustafa Kamal; Timothy J. Krupnik; Md Abdullah Aziz; AFM Tariqul Islam (Journal of Environmental Management, 2024)

Recent advances in production and applications of ectoine, a compatible solute of industrial relevance - Pratik Kadam; Mitesh Khisti; Varun Ravishankar; Vitthal Barvkar; Dhiraj Dhotre; Avinash Sharma; Yogesh Shouche; Smita Zinjarde (Bioresource Technology, 2024)

Overexpressing the glutaredoxin (CaGrx) gene enhances the antioxidant defences and improves drought tolerance in chickpea (Cicer arietinum L.) - Varun Kumar; Anil Kumar; Meenakshi; Uma Gupta; Shiv Narayan; Pramod Arvind Shirke; Indraneel Sanyal (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Single-atom nanozymes with peroxidase-like activity: A review - Eslam M. Hamed; Varun Rai; Sam F.Y. Li (Chemosphere, 2024)

Chrysanthemum wilt caused by Fusarium incarnatum: Etiology unveiled through polyphasic taxonomic methods - Alexander Balamurugan; Mushineni Ashajyothi; Kumar Shanu; Krishnappa Charishma; Hiremath Varun; Kumar Gunjeet; Aundy Kumar (Physiological and Molecular Plant Pathology, 2024)

Development of production and environmental platforms for the European aggregates and minerals industries - Gauti Asbjörnsson; Adam Sköld; Sadeq Zougari; Ann-Gaelle Yar; Nemer Kamel; Sophie Turlur-Chabanon; Kanishk Bhadani; Varun Gowda; Christina Lee; Erik Hulthén; Magnus Evertsson (Minerals Engineering, 2024)

Unlocking sustainable success: Strategic approaches to carbon neutrality - Yubing Sui; Adeel Luqman; Varun Chotia; Girish Jain; Ankit Mehrotra (Journal of Cleaner Production, 2024)

Chitosan-based Schiff bases: Promising materials for biomedical and industrial applications - Varun Pawariya; Soumik De; Joydeep Dutta (Carbohydrate Polymers, 2024)

Physiological alterations and heavy metal accumulation in the transplanted lichen Pyxine cocoes (Sw.) Nyl. in Lucknow city, Uttar Pradesh - Kirti Kumari; Varun Kumar; Sanjeeva Nayaka; Gauri Saxena; Indraneel Sanyal (Environmental Monitoring and Assessment, 2024)

Recent events of land subsidence in Alaknanda valley: a case study of sinking holy town Joshimath, Uttarakhand, India - Divya Singh; Deepesh Goyal; Prakash Biswakarma; Varun Joshi (Environment, Development and Sustainability, 2023)

Exploration of bioactive molecules from Tinospora cordifolia and Actinidia deliciosa as an immunity modulator via molecular docking and molecular dynamics simulation study - Varun Kishor Bagal; Sanket Somnath Rathod; Muskan Musa Mulla; Swaranjali Chandrakant Pawar; Prafulla Balkrishna Choudhari; Vijaykumar Tanajirao Pawar; Deepak Vamanrao Mahuli (Natural Product Research, 2023)

Detection and quantification of TIMP1 and miR-141 through RT-LAMP and TT-LAMP in serum samples during estrous cycle in buffalo - Mansi Joshi; Rajeev Chandel; Varun Kumar; Sanjay Sharma; Rubina Kumari Baithalu; Dheer Singh; Suneel Kumar Onteru (Reproductive Biology, 2023)

Highly sensitive detection of hazardous hydroquinone and chloramphenicol in the presence of paracetamol using cobalt tungstate (CoWO4) nanoplates modified electrode - Varun Pratap Singh; Gajendar Singh; Rajendra Patel; Umesh Kumar Gaur; Manu Sharma (Journal of Environmental Chemical Engineering, 2023)

Spatio-temporal variability analysis of evapotranspiration, water use efficiency and net primary productivity in the semi-arid region of Aravalli and Siwalik range, India - Shubham Kumar; Ritesh Kumar; Manoj Kumar; Alok Kumar Pandey; Prashant K. Srivastava; Sanchit Kumar; Varun Narayan Mishra; V. S. Arya (Environment, Development and Sustainability, 2023)

RETRACTED ARTICLE: An ensemble learning–based experimental framework for smart landslide detection, monitoring, prediction, and warning in IoT-cloud environment - Aman Sharma; Rajni Mohana; Ashima Kukkar; Varun Chodha; Pranjal Bansal (Environmental Science and Pollution Research, 2023)

Smallholder farmer resilience to extreme weather events in a global food value chain - William J. Thompson; Varun Varma; Jonas Joerin; Solhanlle Bonilla-Duarte; Daniel P. Bebber; Wilma Blaser-Hart; Birgit Kopainsky; Leonhard Späth; Bianca Curcio; Johan Six; Pius Krütli (Climatic Change, 2023)
Extreme weather events have severe impacts on food systems, especially for smallholders in global food value chains (GFVCs). There is an urgent need to understand (a) how climate shocks manifest in food systems, and (b) what strategies can enhance food system resilience. Integrating satellite, household and trade data, we investigate the cascading impacts after two consecutive hurricanes on smallholder banana farmers in Dominican Republic, and determinants of their recovery. We found that farmers experienced an ‘all-or-nothing’ pattern of damage, where 75% of flooded farmers lost > 90% of production. Recovery of regional production indicators took ca. 450 days. However, farm-level recovery times were highly variable, with both topographic and human capital factors determining recovery. Utilising this case study, we show that engaging in a GFVC impeded recovery via ‘double exposure’ of production loss and losing market access. Our results suggest that strategies to enhance resilience, with a particular focus on recovery, in GFVCs should promote trader loyalty, facilitate basin-scale collaboration and expand risk-targeted training.

Application of high throughput in vitro metabolomics for hepatotoxicity mode of action characterization and mechanistic-anchored point of departure derivation: a case study with nitrofurantoin - Sabina Ramirez-Hincapie; Barbara Birk; Philipp Ternes; Varun Giri; Franziska Maria Zickgraf; Volker Haake; Michael Herold; Hennicke Kamp; Peter Driemert; Robert Landsiedel; Elke Richling; Dorothee Funk-Weyer; et al. (Archives of Toxicology, 2023)
Omics techniques have been increasingly recognized as promising tools for Next Generation Risk Assessment. Targeted metabolomics offer the advantage of providing readily interpretable mechanistic information about perturbed biological pathways. In this study, a high-throughput LC–MS/MS-based broad targeted metabolomics system was applied to study nitrofurantoin metabolic dynamics over time and concentration and to provide a mechanistic-anchored approach for point of departure (PoD) derivation. Upon nitrofurantoin exposure at five concentrations (7.5 µM, 15 µM, 20 µM, 30 µM and 120 µM) and four time points (3, 6, 24 and 48 h), the intracellular metabolome of HepG2 cells was evaluated. In total, 256 uniquely identified metabolites were measured, annotated, and allocated in 13 different metabolite classes. Principal component analysis (PCA) and univariate statistical analysis showed clear metabolome-based time and concentration effects. Mechanistic information evidenced the differential activation of cellular pathways indicative of early adaptive and hepatotoxic response. At low concentrations, effects were seen mainly in the energy and lipid metabolism, in the mid concentration range, the activation of the antioxidant cellular response was evidenced by increased levels of glutathione (GSH) and metabolites from the de novo GSH synthesis pathway. At the highest concentrations, the depletion of GSH, together with alternations reflective of mitochondrial impairments, were indicative of a hepatotoxic response. Finally, a metabolomics-based PoD was derived by multivariate PCA using the whole set of measured metabolites. This approach allows using the entire dataset and derive PoD that can be mechanistically anchored to established key events. Our results show the suitability of high throughput targeted metabolomics to investigate mechanisms of hepatoxicity and derive point of departures that can be linked to existing adverse outcome pathways and contribute to the development of new ones.

Question 63: What role is played by multidisciplinary dialogue to achieve sustainable development goals? - Ian W. Makin; Damien Pearson; Varun Ravi (Irrigation and Drainage, 2023)
Congress Question 63 ‘What role is played by multidisciplinary dialogue to achieve sustainable development goals?’ sought to explore how a multidisciplinary approach can be enhanced with improved interactions and new layers to engage in the attainment of sustainable development goals (SDGs) more effectively. In addressing these questions, some 39 papers summarized findings from about 24 countries representing substantially different economic situations, climate, farming systems and water resources. The papers illustrated the potential of irrigated agriculture to help end poverty (SDG 1), end hunger (SDG 2), to promote collaboration and investments (SDG 17) and sustain water‐related ecosystems (SDG 14 and SDG 15). The papers highlight the need for increased, and improved, exchange of information among multiple stakeholders involved in agricultural production systems, from field level, through the supply chain, to the consumers of the food and fibre created. Furthermore, a continued focus on capacity development among stakeholders in the sector is essential with improved communication of the value and challenges of agricultural water management beyond the immediate stakeholders (farmers, system operators, water sector regulators, etc.). As greater attention is directed towards the role of agricultural water use in the management of water resources and related ecosystems, the irrigation and drainage profession must communicate more effectively with the broader society to maintain a ‘social license to operate’.

Modeling versatile and dynamic anaerobic metabolism for PAOs/GAOs competition using agent-based model and verification via single cell Raman Micro-spectroscopy - Guangyu Li; Nicholas B. Tooker; Dongqi Wang; Varun Srinivasan; James L. Barnard; Andrew Russell; Beverley Stinson; Jim McQuarrie; Peter Schauer; Adrienne Menniti; Erika Varga; Hélène Hauduc; et al. (Water Research, 2023)

Wild animals enhance climate solutions across social-ecological systems - Varun R. Goswami (Trends in Ecology & Evolution, 2023)

Consequences of elevated CO2 on soil acidification, cation depletion, and inorganic carbon: A column-based experimental investigation - Jannatul Ferdush; Varun Paul; Jac Varco; Keri Jones; Sankar Manalilkada Sasidharan (Soil and Tillage Research, 2023)

Comparative transcriptomic analysis of the chickpea glutaredoxin (CaGrx) gene over-expressed in Arabidopsis thaliana is associated with drought tolerance by modulating the plant defense system - Anil Kumar; Nasreen Bano; Mohd Akram Ansari; Varun Kumar; Sumit K. Bag; Indraneel Sanyal (Acta Physiologiae Plantarum, 2023)

Prognostic Potential of Thrombocyte Indices, Acute Phase Proteins, Electrolytes and Acid-Base Markers in Canine Parvovirus Infected Dogs With Systemic Inflammatory Response Syndrome - Babul Rudra Paul; Ujjwal Kumar De; Varun Kumar Sarkar; Jitendra Singh Gandhar; Manas Kumar Patra; Mithilesh Kumar Singh; Srishti Soni; Chethan Gollahalli Eregowda (Topics in Companion Animal Medicine, 2023)

Soil health assessment for different tillage and cropping systems to determine sustainable management practices in a humid region - Tingting Chang; Gary Feng; Varun Paul; Ardeshir Adeli; John P. Brooks; Johnie Norton Jenkins (Soil and Tillage Research, 2023)

Sustainability assessment framework of biomedical scaffolds: Additive manufacturing versus traditional manufacturing - Neha Choudhary; Varun Sharma; Pradeep Kumar (Journal of Cleaner Production, 2023)

Uranium uptake by phosphate minerals at hydrothermal conditions - Ángel Jiménez-Arroyo; Rinat Gabitov; Artas Migdisov; Juejing Lui; Andrew Strzelecki; Xiaodong Zhao; Xiaofeng Guo; Varun Paul; Todd Mlsna; Alberto Perez-Huerta; Florie Caporuscio; Hongwu Xu; et al. (Chemical Geology, 2023)

A metabolomics approach to reveal the mechanism of developmental toxicity in zebrafish embryos exposed to 6-propyl-2-thiouracil - Pia Wilhelmi; Varun Giri; Franziska Maria Zickgraf; Volker Haake; Stefan Henkes; Peter Driemert; Paul Michaelis; Wibke Busch; Stefan Scholz; Burkhard Flick; Marta Barenys; Barbara Birk; et al. (Chemico-Biological Interactions, 2023)

Rainfall-Runoff modelling using SWAT and eight artificial intelligence models in the Murredu Watershed, India - Padala Raja Shekar; Aneesh Mathew; Arun P. S.; Varun P. Gopi (Environmental Monitoring and Assessment, 2023)

Action of nanoparticles in the amelioration of heavy metal phytotoxicity - Afsana Praveen; Shilpy Singh; Varun Kumar Sharma (Cereal Research Communications, 2023)

Sustainable synthesis of multifunctional nanomaterials from rice wastes: a comprehensive review - Subhendu Chakroborty; Kaushik Pal; Nibedita Nath; Varun Singh; Arundhati Barik; Siba Soren; Pravati Panda; Nidhi Asthana; George Z. Kyzas (Environmental Science and Pollution Research, 2023)
More than 60% of India’s population relies on agriculture as their primary source of income, making it the nation’s most important economic sector. Rice husk (often abbreviated as RH) is one of the most typical by-products of agricultural production. Every five tonnes of rice that is harvested results in the production of one tonne of husk. The concept of recycling and reusing waste from agricultural production has received interest from a variety of environmental and industrial perspectives. A wide variety of nanomaterials, including nano-zeolite, nanocarbon, and nano-silica, have been discovered in agro-waste. From rice cultivation to the finished product, there was a by-product consisting of husk that comprised 20% of the overall weight, or RH. The percentage of silica in RH ash ranges from 60 to 40%, with the remaining percentage consisting of various minerals. As a direct consequence of this, several distinct approaches to generating and extracting nanomaterial from rice husk have been developed. Because it contains a significant amount of cellulose and lignin, RH is an excellent and economical source of carbon precursor. The goal of this chapter is to produce carbon-based nanomaterials from RH.

Investigation of molecular mechanisms of Ulmus davidiana against gastric cancer: A network pharmacology study incorporating gene expression data and molecular docking analysis - Shivam Bhola; Varun Jaiswal; Hae-Jeung Lee (South African Journal of Botany, 2023)

The mitochondrially targeted peptide elamipretide (SS-31) improves ADP sensitivity in aged mitochondria by increasing uptake through the adenine nucleotide translocator (ANT) - Gavin Pharaoh; Varun Kamat; Sricharan Kannan; Rudolph S. Stuppard; Jeremy Whitson; Miguel Martín-Pérez; Wei-Jun Qian; Michael J. MacCoss; Judit Villén; Peter Rabinovitch; Matthew D. Campbell; Ian R. Sweet; et al. (GeroScience, 2023)
Aging muscle experiences functional decline in part mediated by impaired mitochondrial ADP sensitivity. Elamipretide (ELAM) rapidly improves physiological and mitochondrial function in aging and binds directly to the mitochondrial ADP transporter ANT. We hypothesized that ELAM improves ADP sensitivity in aging leading to rescued physiological function. We measured the response to ADP stimulation in young and old muscle mitochondria with ELAM treatment, in vivo heart and muscle function, and compared protein abundance, phosphorylation, and S-glutathionylation of ADP/ATP pathway proteins. ELAM treatment increased ADP sensitivity in old muscle mitochondria by increasing uptake of ADP through the ANT and rescued muscle force and heart systolic function. Protein abundance in the ADP/ATP transport and synthesis pathway was unchanged, but ELAM treatment decreased protein s-glutathionylation incuding of ANT. Mitochondrial ADP sensitivity is rapidly modifiable. This research supports the hypothesis that ELAM improves ANT function in aging and links mitochondrial ADP sensitivity to physiological function. Graphical abstract ELAM binds directly to ANT and ATP synthase and ELAM treatment improves ADP sensitivity, increases ATP production, and improves physiological function in old muscles. ADP (adenosine diphosphate), ATP (adenosine triphosphate), VDAC (voltage-dependent anion channel), ANT (adenine nucleotide translocator), H + (proton), ROS (reactive oxygen species), NADH (nicotinamide adenine dinucleotide), FADH 2 (flavin adenine dinucleotide), O 2 (oxygen), ELAM (elamipretide), –SH (free thiol), –SSG (glutathionylated protein)

Thermo-hydraulic performance of solar air heater having discrete D-shaped ribs as artificial roughness - Nitesh Dutt; Ankush Jageshwar Hedau; Ashwani Kumar; Mukesh Kumar Awasthi; Varun Pratap Singh; Gaurav Dwivedi (Environmental Science and Pollution Research, 2023)

Solvent-free and low temperature synthesis of chalcogenide Na superionic conductors for solid-state batteries - Selim Halacoglu; Yang Li; William Arnold; Varun Shreyas; Xiaolin Guo; Jacek B. Jasinski; Badri Narayanan; Hui Wang (Chemical Engineering Journal, 2023)

Deficiency of the mitochondrial ribosomal subunit, MRPL50, causes autosomal recessive syndromic premature ovarian insufficiency - Shabnam Bakhshalizadeh; Daniella H. Hock; Nicole A. Siddall; Brianna L. Kline; Rajini Sreenivasan; Katrina M. Bell; Franca Casagranda; Sadishkumar Kamalanathan; Jayaprakash Sahoo; Niya Narayanan; Dukhabandhu Naik; Varun Suryadevara; et al. (Human Genetics, 2023)
Premature ovarian insufficiency (POI) is a common cause of infertility in women, characterised by amenorrhea and elevated FSH under the age of 40 years. In some cases, POI is syndromic in association with other features such as sensorineural hearing loss in Perrault syndrome. POI is a heterogeneous disease with over 80 causative genes known so far; however, these explain only a minority of cases. Using whole-exome sequencing (WES), we identified a MRPL50 homozygous missense variant (c.335T > A; p.Val112Asp) shared by twin sisters presenting with POI, bilateral high-frequency sensorineural hearing loss, kidney and heart dysfunction. MRPL50 encodes a component of the large subunit of the mitochondrial ribosome. Using quantitative proteomics and western blot analysis on patient fibroblasts, we demonstrated a loss of MRPL50 protein and an associated destabilisation of the large subunit of the mitochondrial ribosome whilst the small subunit was preserved. The mitochondrial ribosome is responsible for the translation of subunits of the mitochondrial oxidative phosphorylation machinery, and we found patient fibroblasts have a mild but significant decrease in the abundance of mitochondrial complex I. These data support a biochemical phenotype associated with MRPL50 variants. We validated the association of MRPL50 with the clinical phenotype by knockdown/knockout of mRpL50 in Drosophila , which resulted abnormal ovarian development. In conclusion, we have shown that a MRPL50 missense variant destabilises the mitochondrial ribosome, leading to oxidative phosphorylation deficiency and syndromic POI, highlighting the importance of mitochondrial support in ovarian development and function.

Gangotri glacier dynamics from multi-sensor SAR and optical data - Praveen Kumar Thakur; Anukesh Krishnankutty Ambika; Sanjay M. Bisht; Alfred Stein; Anirudha Mahagaonkar; Uday Kumar; Vaibhav Garg; Varun Khajuria; Arpit Chouksey; Snehmani; Prakash Chauhan; SP Aggarwal (Advances in Space Research, 2023)

Effect of Exercise on β-Endorphin and Its Receptors in Myasthenia Gravis Patients - Gyanesh M. Tripathi; Usha K. Misra; Jayantee Kalita; Varun K. Singh; Abhilasha Tripathi (Molecular Neurobiology, 2023)

Comparative single-cell analysis of the adult heart and coronary vasculature - Saranya Balachandran; Jelena Pozojevic; Varun K. A. Sreenivasan; Malte Spielmann (Mammalian Genome, 2023)
The structure and function of the circulatory system, including the heart, have undergone substantial changes with the vertebrate evolution. Although the basic function of the heart is to pump blood through the body, its size, shape, speed, regeneration capacity, etc. vary considerably across species. Here, we address the differences among vertebrate hearts using a single-cell transcriptomics approach. Published datasets of macaque ( Macaca fascicularis ), mouse, and zebrafish hearts were integrated and compared to the human heart as a reference. While the three mammalian hearts integrated well, the zebrafish heart showed very little overlap with the other species. Our analysis revealed a mouse-specific cell subpopulation of ventricular cardiomyocytes (CM), represented by strikingly different expression patterns of specific genes related to high-energy metabolism. Interestingly, the observed differences between mouse and human CM coincided with actual biological differences between the two species. Smooth muscle and endothelial cells (EC) exhibited species-specific differences in clustering and gene expression, respectively, which we attribute to the tissues selected for sequencing, given different focuses of the original studies. Finally, we compared human and zebrafish heart-specific fibroblasts (FB) and identified a distinctively high expression of genes associated with heart regeneration following injury in zebrafish. Together, our results show that integration of numerous datasets of different species and different sequencing technologies is feasible and that this approach can identify species-specific differences and similarities in the heart.

Freely Available Datasets Able to Simulate the Snowmelt Runoff in Himalayan Basin with the Aid of Temperature Index Modelling - Asha Thapliyal; Varun Khajuria; Praveen Kumar Thakur; Sanjeev Kimothi; Mahendra Pratap Singh Bisht; Prakash Chauhan (Journal of the Indian Society of Remote Sensing, 2023)

Effect of Metal-resistant PGPB on the Metal Uptake, Antioxidative Defense, Physiology, and Growth of Atriplex lentiformis (Torr.) S.Wats. in Soil Contaminated with Cadmium and Nickel - Harsh Kumar; Shumailah Ishtiyaq; Paulo J. C. Favas; Mayank Varun; Manoj S. Paul (Journal of Plant Growth Regulation, 2023)

Redesigning the Clinical Trial Development Process as a Global Pharmaceutical Firm: Gaining Velocity via Lean-Sprint - Varun Paul; Lori B. Ferranti; David M. Dilts (Journal of Pharmaceutical Innovation, 2023)

Thalidomide interaction with inflammation in idiopathic pulmonary fibrosis - Nikitha Naomi Dsouza; Varun Alampady; Krishnaprasad Baby; Swastika Maity; Bharath Harohalli Byregowda; Yogendra Nayak (Inflammopharmacology, 2023)
The “Thalidomide tragedy” is a landmark in the history of the pharmaceutical industry. Despite limited clinical trials, there is a continuous effort to investigate thalidomide as a drug for cancer and inflammatory diseases such as rheumatoid arthritis, lepromatous leprosy, and COVID-19. This review focuses on the possibilities of targeting inflammation by repurposing thalidomide for the treatment of idiopathic pulmonary fibrosis (IPF). Articles were searched from the Scopus database, sorted, and selected articles were reviewed. The content includes the proven mechanisms of action of thalidomide relevant to IPF. Inflammation, oxidative stress, and epigenetic mechanisms are major pathogenic factors in IPF. Transforming growth factor-β (TGF-β) is the major biomarker of IPF. Thalidomide is an effective anti-inflammatory drug in inhibiting TGF-β, interleukins (IL-6 and IL-1β), and tumour necrosis factor-α (TNF-α). Thalidomide binds cereblon, a process that is involved in the proposed mechanism in specific cancers such as breast cancer, colon cancer, multiple myeloma, and lung cancer. Cereblon is involved in activating AMP-activated protein kinase (AMPK)-TGF-β/Smad signalling, thereby attenuating fibrosis. The past few years have witnessed an improvement in the identification of biomarkers and diagnostic technologies in respiratory diseases, partly because of the COVID-19 pandemic. Hence, investment in clinical trials with a systematic plan can help repurpose thalidomide for pulmonary fibrosis. Graphical Abstract

Quantitative analysis of human hairs and nails - Varun Bali; Yugal Khajuria; Vidit Maniyar; Pradeep K. Rai; Upendra Kumar; Charles Ghany; M.A. Gondal; Vivek K. Singh (Biophysical Reviews, 2023)

Correction to: Evidence of Strong Flux Underestimation by Bulk Parametrizations During Drifting and Blowing Snow - Armin Sigmund; Jérôme Dujardin; Francesco Comola; Varun Sharma; Hendrik Huwald; Daniela Brito Melo; Naohiko Hirasawa; Kouichi Nishimura; Michael Lehning (Boundary-Layer Meteorology, 2023)

Effect of systemic inflammatory response syndrome on thrombocytogram, acute phase proteins, electrolytes, acid-base indices and cytokine expression in naturally canine parvovirus infected dogs - Babul R. Paul; Ujjwal K. De; Varun K. Sarkar; Jitendra S. Gandhar; Manas K. Patra; Ravi K. Agrawal; Mithilesh K. Singh; Srishti Soni; Chethan G. Eregowda (Veterinary Immunology and Immunopathology, 2023)

Deep tubewell use is associated with increased household microbial contamination in rural Bangladesh: Results from a prospective cohort study among households in rural Bangladesh - Varun Goel; Brianna Chan; Mia Ziade; Md. Yunus; Md. Taslim Ali; Md. Al Fazal Khan; Md. Nurul Alam; ASG Faruque; Shahabuddin Babu; Md.Masnoon Kabir; Paul L. Delamater; Marc Serre; et al. (Environmental Pollution, 2023)

Tropical agricultural wooded land uses support high site use of forest birds - Biang La Nam Syiem; Don A. Driscoll; Divya Vasudev; Varun R. Goswami (Biological Conservation, 2023)

Multiscale phenological niches of seed fall in diverse A mazonian plant communities - Damie Pak; Varun Swamy; Patricia Alvarez‐Loayza; Fernando Cornejo‐Valverde; Simon A. Queenborough; Margaret R. Metz; John Terborgh; Renato Valencia; S. Joseph Wright; Nancy C. Garwood; Jesse R. Lasky (Ecology, 2023)
Phenology has long been hypothesized as an avenue for niche partitioning or interspecific facilitation, both promoting species coexistence. Tropical plant communities exhibit striking diversity in reproductive phenology, but many are also noted for large synchronous reproductive events. Here we study whether the phenology of seed fall in such communities is nonrandom, the temporal scales of phenological patterns, and ecological factors that drive reproductive phenology. We applied multivariate wavelet analysis to test for phenological synchrony versus compensatory dynamics (i.e., antisynchronous patterns where one species' decline is compensated by the rise of another) among species and across temporal scales. We used data from long‐term seed rain monitoring of hyperdiverse plant communities in the western Amazon. We found significant synchronous whole‐community phenology at multiple timescales, consistent with shared environmental responses or positive interactions among species. We also observed both compensatory and synchronous phenology within groups of species (confamilials) likely to share traits and seed dispersal mechanisms. Wind‐dispersed species exhibited significant synchrony at ~6‐month scales, suggesting these species might share phenological niches to match the seasonality of wind. Our results suggest that community phenology is shaped by shared environmental responses but that the diversity of tropical plant phenology may partly result from temporal niche partitioning. The scale‐specificity and time‐localized nature of community phenology patterns highlights the importance of multiple and shifting drivers of phenology.

Early adaptive responses in the skeletal muscle of young mice with hereditary hemochromatosis - Varun V. Dhorajia; Jonghan Kim; Yuho Kim (Molecular Biology Reports, 2023)

Integration, coordination, and regulatory resources: Keys to electricity system resilience - Varun Rai (The Electricity Journal, 2023)

Identifying sustainable coexistence potential by integrating willingness-to-coexist with habitat suitability assessments - Susanne Marieke Vogel; Divya Vasudev; Joseph O. Ogutu; Purity Taek; Emilio Berti; Varun R. Goswami; Michael Kaelo; Robert Buitenwerf; Michael Munk; Wang Li; Jake Wall; Desalegn Chala; et al. (Biological Conservation, 2023)

Enhanced photocatalytic activity of TiO2–NiO heterojunctions supported on alumina for malachite green degradation - Y. Varun; H. Augustus; N. Panda; I. Sreedhar; S. A. Singh (International Journal of Environmental Science and Technology, 2023)

Towards the effect of climate change in structural loads of urban infrastructure: A review - Varun Mishra; Ayan Sadhu (Sustainable Cities and Society, 2023)

Application of machine learning approaches to predict the impact of ambient air pollution on outpatient visits for acute respiratory infections - Khaiwal Ravindra; Samsher Singh Bahadur; Varun Katoch; Sanjeev Bhardwaj; Maninder Kaur-Sidhu; Madhu Gupta; Suman Mor (Science of The Total Environment, 2023)

Exploration of anticancer potential of Lantadenes from weed Lantana camara: Synthesis, in silico, in vitro and in vivo studies - Monika Chauhan; Zahid Ahmad Dhar; Varun Gorki; Sonia Sharma; Ashwani Koul; Shashi Bala; Ramandeep Kaur; Sukhbir Kaur; Manu Sharma; Neelima Dhingra (Phytochemistry, 2023)

Magnetically engineered sulfurized peat-based activated carbon for remediation of emerging pharmaceutical contaminants - Varun Shukla; Deepak Panchal; Om Prakash; Prasenjit Mondal; Isha Hiwrale; Rita S. Dhodapkar; Sukdeb Pal (Bioresource Technology, 2023)

Growth studies in commercial broiler birds offered citric acid in formulated feed with low mineral density - Shivani Katoch; Sumani Sharma; Varun Sankhyan; Daisy Wadhwa; Arun Sharma; Sanjiv Kumar (Tropical Animal Health and Production, 2023)

Early-Life Intervention of Lactoferrin and Probiotic in Suckling Piglets: Effects on Immunoglobulins, Intestinal Integrity, and Neonatal Mortality - Varun Kumar Sarkar; Ujjwal Kumar De; Anju Kala; Ashok Kumar Verma; Anuj Chauhan; Babul Rudra Paul; Srishti Soni; Jitendra Singh Gandhar; Pallab Chaudhuri; Manas Kumar Patra; Chethan Gollahalli Eregowda; Gyanendra Kumar Gaur (Probiotics and Antimicrobial Proteins, 2023)

Metformin and Dapagliflozin Attenuate Doxorubicin-Induced Acute Cardiotoxicity in Wistar Rats: An Electrocardiographic, Biochemical, and Histopathological Approach - Shakta Mani Satyam; Laxminarayana Kurady Bairy; Prakashchandra Shetty; P. Sainath; Sanjay Bharati; Akheruz Zaman Ahmed; Varun Kumar Singh; A. J. Ashwal (Cardiovascular Toxicology, 2023)
Doxorubicin is a widely used anticancer drug whose efficacy is limited due to its cardiotoxicity. There is no ideal cardioprotection available against doxorubicin-induced cardiotoxicity. This study aimed to investigate the anticipated cardioprotective potential of metformin and dapagliflozin against doxorubicin-induced acute cardiotoxicity in Wistar rats. At the beginning of the experiment, cardiac screening of experimental animals was done by recording an electrocardiogram (ECG) before allocating them into the groups. Thereafter, a total of thirty healthy adult Wistar rats (150–200 g) were randomly divided into five groups ( n = 6) and treated for eight days as follows: group I (normal control), group II (doxorubicin control), group III (metformin 250 mg/kg/day), group IV (metformin 180 mg/kg/day), and group V (dapagliflozin 0.9 mg/kg/day). On the 7th day of the treatment phase, doxorubicin 20 mg/kg was administered intraperitoneal to groups II, III, IV, and V. On the 9th day (immediately after 48 h of doxorubicin administration), blood was collected from anesthetized animals for glucose, lipid profile, CK-MB & AST estimation, and ECG was recorded. Later, animals were sacrificed, and the heart was dissected for histopathological examination. We found that compared to normal control rats, CK-MB, AST, and glucose were significantly increased in doxorubicin control rats. There was a significant reversal of doxorubicin-induced hyperglycemia in the rats treated with metformin 250 mg/kg compared to doxorubicin control rats. Both metformin (180 mg/kg and 250 mg/kg) and dapagliflozin (0.9 mg/kg) significantly altered doxorubicin-induced ECG changes and reduced the levels of cardiac injury biomarkers CK-MB and AST compared to doxorubicin control rats. Metformin and dapagliflozin protected the cellular architecture of the myocardium from doxorubicin-induced myocardial injury. Current study revealed that both metformin and dapagliflozin at the FDA-recommended antidiabetic doses mitigated doxorubicin-induced acute cardiotoxicity in Wistar rats. The obtained data have opened the perspective to perform chronic studies and then to clinical studies to precisely consider metformin and dapagliflozin as potential chemoprotection in the combination of chemotherapy with doxorubicin to limit its cardiotoxicity, especially in patients with comorbid conditions like type II diabetes mellitus.

Quantifying Cardiothoracic Variation with Posture and Respiration to Inform Cardiac Device Design - Geeth A. Kondaveeti; Varun A. Bhatia; Ryan P. Lahm; Megan L. Harris; James P. Gaewsky; F. Scott Gayzik; John F. Greenhalgh; Craig A. Hamilton; R. Brandon Stacey; Ashley A. Weaver (Cardiovascular Engineering and Technology, 2023)

Stability of human stress hormones and stress hormone metabolites in wastewater under oxic and anoxic conditions - Varun Kelkar; Erin M. Driver; Elisa J. Bienenstock; Anthony Palladino; Rolf U. Halden (Science of The Total Environment, 2023)

Automated segmentation and classification of hand thermal images in rheumatoid arthritis using machine learning algorithms: A comparison with quantum machine learning technique - R.K. Ahalya; U. Snekhalatha; Varun Dhanraj (Journal of Thermal Biology, 2023)

Multifaceted PVDF nanofibers in energy, water and sensors: A contemporary review (2018 to 2022) and future perspective - S. Varun; Nitish Manu George; Akash M. Chandran; Lity Alen Varghese; Prasanna Kumar S. Mural (Journal of Fluorine Chemistry, 2023)

A novel design for solar collector used for water heating application having nanofluid as working medium: CFD modeling and simulation - Rajneesh Kumar; Manjeet Kharub; Rajesh Sharma; Periapattana Nagaraj Hrisheekesha; Varun Goel; Suvanjan Bhattacharyya; Vineet Veer Tyagi; Varun (Environmental Science and Pollution Research, 2023)

Emergent properties of coupled bistable switches - Kishore Hari; Pradyumna Harlapur; Aditi Gopalan; Varun Ullanat; Atchuta Srinivas Duddu; Mohit Kumar Jolly (Journal of Biosciences, 2022)

New generalized ANN-based hybrid broadband response spectra generator using physics-based simulations - Varun Sharma; J. Dhanya; Maheshreddy Gade; Jayalakshmi Sivasubramonian (Natural Hazards, 2022)

Deep learning approaches based improved light weight U-Net with attention module for optic disc segmentation - R. Shalini; Varun P. Gopi (Physical and Engineering Sciences in Medicine, 2022)

Performance Evaluation of Google Earth Engine Based Precipitation Datasets Under Different Climatic Zones over India - Sukant Jain; Varun Tiwari; Amrit Thapa; Rohit Mangla; R. K. Jaiswal; Vinay Kumar; Supriya Tiwari; Mirela G. Tulbure; Ravi Galkate; A. K. Lohani; Kamal Pandey (Remote Sensing in Earth Systems Sciences, 2022)

Divulging the anti-acetylcholinesterase activity of Colletotrichum lentis strain KU1 extract as sustainable AChE active site inhibitors - Anoop Kallingal; Aravind Ayyolath; Varun Thachan Kundil; Akshay Maniyeri Suresh; Tomy Muringayil Joseph; Józef Haponiuk; Sabu Thomas; Anu Augustine (Archives of Microbiology, 2022)

Correction to: Spatio-temporal variability and trend analysis of rainfall in Wainganga river basin, Central India, and forecasting using state-space models - Nanabhau S. Kudnar; Pranaya Diwate; Varun Narayan Mishra; Prashant K. Srivastava; Akshay Kumar; Manish Pandey (Theoretical and Applied Climatology, 2022)

Spatio-temporal variability and trend analysis of rainfall in Wainganga river basin, Central India, and forecasting using state-space models - Nanabhau S. Kudnar; Pranaya Diwate; Varun Narayan Mishra; Prashant K. Srivastava; Akshay Kumar; Manish Pandey (Theoretical and Applied Climatology, 2022)

Cricetid rodents from the Middle Miocene Siwalik exposure of Kalaunta (Jammu), NW Himalaya, India - Varun Parmar; Rigzin Norboo; Rahul Magotra; Deepak Singh Kshetrimayum (Arabian Journal of Geosciences, 2022)

A questionnaire-based survey of acceptability and satisfaction of virtual neurology clinic during COVID-19 lockdown: a preliminary study - Anand Kumar; Neha Lall; Abhishek Pathak; Deepika Joshi; Vijaya Nath Mishra; Rameshwar Nath Chaurasia; Varun Kumar Singh (Acta Neurologica Belgica, 2022)

Lipid- and TPGS-Based Core–Shell-Type Nanocapsules Endowed with High Paclitaxel Loading and Enhanced Anticancer Potential - Sameer S. Katiyar; Ravindra Patil; Rohan Ghadi; Kaushik Kuche; Varun Kushwah; Chander Parkash Dora; Sanyog Jain (AAPS PharmSciTech, 2022)

Impact of Extractables/Leachables from Filter Materials on the Stability of Protein-Based Pharmaceutical Products - Varun Kushwah; Juliana Münzer; Verena Feenstra; Stefan Mohr; Amrit Paudel (AAPS PharmSciTech, 2022)
The manufacturing of biopharmaceutical drug solutions can involve close contact with various polymeric components, including common filter membranes. Potential leachable substances from filters may interact with the protein and thereby increase the structural damage and aggregation. The main aim of the study deals with the assessment of extractable and leachable (E/L) from different filters and the potential effect of E/Ls on protein (human granulocyte-colony stimulating factor (rh-GCSF) stability. The present study examines the E/L profile of five different polymeric filter membranes using various chromatographic techniques including LC–MS and GC–MS. In order to investigate their effect on protein stability, G-CSF (human granulocyte colony-stimulating factor) formulations were spiked with filter leachable stock solutions at two different pH levels. The spiked formulations were further analyzed with respect to their aggregation behavior. The results demonstrated a higher E/L content in the case of polyamide (PA), polycarbonate (PC), and polyethersulfone (PES) filters as compared to the polytetrafluoroethylene (PTFE) and regenerative cellulose (RC) filter materials. The E/L from RC and PES was found surface-active, whereas E/L from PA and RC significantly altered the particle size/structure resulting in the aggregation of proteins. Furthermore, bisphenol A was found to be one of the E/L substances from PC filters and can impose significant health problems when administered along with pharmaceutical products. The present study reports a qualitative rank ordering of the filter membranes in terms of their propensity to generate E/Ls and thus can be helpful in selecting a suitable membrane filter.

Correction to: Nanocurcumin protects cardiomyoblasts H9c2 from hypoxia-induced hypertrophy and apoptosis by improving oxidative balance - Sarita Nehra; Varun Bhardwaj; Namita Kalra; Lilly Ganju; Anju Bansal; Shweta Saxena; Deepika Saraswat (Journal of Physiology and Biochemistry, 2022)

Solar cooking innovations, their appropriateness, and viability - Abhishek Saxena; Brian Norton; Varun Goel; Desh Bandhu Singh (Environmental Science and Pollution Research, 2022)

DNA barcoding of fruit flies associated with cucurbit ecosystem and combination of Cue-Lure and Methyl Eugenol in trap is not effective for mass trapping of responsive fruit flies - Varun Arya; Srinivasa Narayana; Saniya Tyagi; Samantapudi Venkata Satyanarayana Raju; Chandra Prakash Srivastava; Twinkle Sinha; Pratap Divekar (Phytoparasitica, 2022)

Assessment of Different Spectral Unmixing Techniques on Space Borne Hyperspectral Imagery - Vinay Kumar; Kamal Pandey; Chinmaya Panda; Varun Tiwari; Shefali Agrawal (Remote Sensing in Earth Systems Sciences, 2022)

Relating individual motion sickness levels to subjective discomfort ratings - Ksander N. de Winkel; Tuğrul Irmak; Varun Kotian; Daan M. Pool; Riender Happee (Experimental Brain Research, 2022)
High levels of vehicle automation are expected to increase the risk of motion sickness, which is a major detriment to driving comfort. The exact relation between motion sickness and discomfort is a matter of debate, with recent studies suggesting a relief of discomfort at the onset of nausea. In this study, we investigate whether discomfort increases monotonously with motion sickness and how the relation can best be characterized in a semantic experiment (Experiment 1) and a motion sickness experiment (Experiment 2). In Experiment 1, 15 participants performed pairwise comparisons on the subjective discomfort associated with each item on the popular MIsery SCale (MISC) of motion sickness. In Experiment 2, 17 participants rated motion sickness using the MISC during exposures to four sustained motion stimuli, and provided (1) numerical magnitude estimates of the discomfort experienced for each level of the MISC, and (2) verbal magnitude estimates with seven qualifiers, ranging between feeling ‘excellent’ and ‘terrible’. The data of Experiment 1 show that the items of the MISC are ranked in order of appearance, with the exception of 5 (‘severe dizziness, warmth, headache, stomach awareness, and sweating’) and 6 (‘slight nausea’), which are ranked in opposite order. However, in Experiment 2, we find that discomfort associated with each level of the MISC, as it was used to express motion sickness during exposure to a sickening stimulus, increases monotonously; following a power law with an exponent of 1.206. While the results of Experiment 1 replicate the non-linearity found in recent studies, the results of Experiment 2 suggest that the non-linearity is due to the semantic nature of Experiment 1, and that there is a positive monotonous relation between MISC and discomfort in practice. These results support the suitability of MISC to assess motion sickness.

Optimization-based design for lignocellulosic ethanol production: a case study of the state of Maharashtra, India - Varun Punnathanam; Yogendra Shastri (Clean Technologies and Environmental Policy, 2022)

CAMTA transcription factor enhances salinity and drought tolerance in chickpea (Cicer arietinum L.) - Meenakshi; Anil Kumar; Varun Kumar; Arvind Kumar Dubey; Shiv Narayan; Samir V. Sawant; Veena Pande; Pramod Arvind Shirke; Indraneel Sanyal (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Photophysics of nanographenes: from polycyclic aromatic hydrocarbons to graphene nanoribbons - Matthew C. Drummer; Varun Singh; Nikita Gupta; Jonathan L. Gesiorski; Ravindra B. Weerasooriya; Ksenija D. Glusac (Photosynthesis Research, 2022)

Evidence of Strong Flux Underestimation by Bulk Parametrizations During Drifting and Blowing Snow - Armin Sigmund; Jérôme Dujardin; Francesco Comola; Varun Sharma; Hendrik Huwald; Daniela Brito Melo; Naohiko Hirasawa; Kouichi Nishimura; Michael Lehning (Boundary-Layer Meteorology, 2022)
The influence of drifting and blowing snow on surface mass and energy exchange is difficult to quantify due to limitations in both measurements and models, but is still potentially very important over large areas with seasonal or perennial snow cover. We present a unique set of measurements that make possible the calculation of turbulent moisture, heat, and momentum fluxes during conditions of drifting and blowing snow. From the data, Monin–Obukhov estimation of bulk fluxes is compared to eddy-covariance-derived fluxes. In addition, large-eddy simulations with sublimating particles are used to more completely understand the vertical profiles of the fluxes. For a storm period at the Syowa S17 station in East Antarctica, the bulk parametrization severely underestimates near-surface heat and moisture fluxes. The large-eddy simulations agree with the eddy-covariance fluxes when the measurements are minimally disturbed by the snow particles. We conclude that overall exchange over snow surfaces is much more intense than current models suggest, which has implications for the total mass balance of the Antarctic ice sheet and the cryosphere.

Hypocholesterolemic Effect of Potent Peptide and Bioactive Fraction from Pigeon Pea By-Products in Wistar Rats - Varun Kumar; S. P. Muthu Kumar; Purnima Kaul Tiku (International Journal of Peptide Research and Therapeutics, 2021)

Effects of piperazine and EDTA in garden snail towards electrolytic variation and antimicrobial activities - Anil Kumar; Varun Dhiman; Pawan Kumar; Deepak Pant (Environmental Science and Pollution Research, 2021)

Developing an effectiveness index for biomedical waste management in Indian states using a composite indicators approach - Anurag Deepak; Dinesh Kumar; Varun Sharma (Environmental Science and Pollution Research, 2021)

Crop Health Assessment Using Sentinel-1 SAR Time Series Data in a Part of Central India - Sandeep Kumar Kaushik; Varun Narayan Mishra; Milap Punia; Pranaya Diwate; Thota Sivasankar; Anil Kumar Soni (Remote Sensing in Earth Systems Sciences, 2021)

Genetic Knockout of the Serotonin Reuptake Transporter Results in the Reduction of Dendritic Spines in In vitro Rat Cortical Neuronal Culture - Daniel Chaji; Varun S. Venkatesh; Tomoaki Shirao; Darren J. Day; Bart A. Ellenbroek (Journal of Molecular Neuroscience, 2021)

Spatial and seasonal variations in particulate matter and gaseous pollutants around integrated industrial estate (IIE), SIDCUL, Haridwar: a case study - Rakesh Bhutiani; Dipali B. Kulkarni; D. R. Khanna; Varun Tyagi; Faheem Ahamad (Environment, Development and Sustainability, 2021)

Diabetic retinopathy classification based on multipath CNN and machine learning classifiers - S. Gayathri; Varun P. Gopi; P. Palanisamy (Physical and Engineering Sciences in Medicine, 2021)

In Vivo Intravascular Pacing Using a Wireless Microscale Stimulator - Parinaz Abiri; Sandra Duarte-Vogel; Tzu-Chieh Chou; Arash Abiri; Varun Gudapati; Alireza Yousefi; Mehrdad Roustaei; Chih-Chiang Chang; Qingyu Cui; Jeffrey J. Hsu; Malcolm Bersohn; Dejan Markovic; et al. (Annals of Biomedical Engineering, 2021)

Chia Seed Oil Ameliorates Doxorubicin-Induced Cardiotoxicity in Female Wistar Rats: An Electrocardiographic, Biochemical and Histopathological Approach - Akheruz Zaman Ahmed; Kamalesh D. Mumbrekar; Shakta Mani Satyam; Prakashchandra Shetty; Melanie Rose D’Souza; Varun Kumar Singh (Cardiovascular Toxicology, 2021)
Doxorubicin (DOX) is a potent anti-cancer antibiotic that was widely used for treatment of various cancers. It produces free radicals which result in extreme dose-limiting cardiotoxicity. This study investigated the cardioprotective potential of chia seed oil, an active polyphenolic nutraceutical against doxorubicin-induced cardiotoxicity in Wistar rats. Twenty-four female Wistar rats were divided into four groups ( n = 6) which consist of normal control, DOX control, test-A and test-B group. Animals were prophylactically treated with two different doses of test drug, i.e. chia seed oil 2.5 ml/kg/day and 5 ml/kg/day in test-A and test-B groups orally for 7 days. Doxorubicin (25 mg/kg; single dose) was administered intraperitoneally to DOX control, Test-A and Test-B animals on the seventh day to induce cardiotoxicity. ECG analysis was done before and after treatment. Besides ECG, CK, CK-MB, LDH, AST, MDA and GSH were analyzed. DOX had significantly altered ECG, CK, CK-MB, LDH, AST, MDA and GSH. Pre-treatment with chia seed oil significantly alleviated DOX-induced ECG changes and also guarded against DOX-induced rise of serum CK, CK-MB and AST levels. Chia seed oil alleviated histopathological alteration in DOX-treated rats. It also significantly inhibited DOX-induced GSH depletion and elevation of MDA. The present study revealed that chia seed oil exerts cardioprotection against doxorubicin-induced cardiotoxicity in female Wistar rats. Our study opens the perspective to clinical studies to precisely consider chia seed oil as a potential chemoprotectant nutraceutical in the combination chemotherapy with doxorubicin to limit its cardiotoxicity.

Fluoride-Induced Expression of Neuroinflammatory Markers and Neurophysiological Regulation in the Brain of Wistar Rat Model - Yugandhar P. Reddy; Santosh Tiwari; Lomas K. Tomar; Nalini Desai; Varun Kumar Sharma (Biological Trace Element Research, 2021)

A Cholesterol Homeostasis by Bioactive Peptide Fraction from Pigeon Pea By-Product: An In-Vitro Study - Varun Kumar; Purnima Kaul Tiku (International Journal of Peptide Research and Therapeutics, 2021)

Chickpea glutaredoxin (CaGrx) gene mitigates drought and salinity stress by modulating the physiological performance and antioxidant defense mechanisms - Anil Kumar; Varun Kumar; Arvind Kumar Dubey; Mohd Akram Ansari; Shiv Narayan; Meenakshi; Sanoj Kumar; Vivek Pandey; Veena Pande; Indraneel Sanyal (Physiology and Molecular Biology of Plants, 2021)

Geographically Weighted Method Integrated with Logistic Regression for Analyzing Spatially Varying Accuracy Measures of Remote Sensing Image Classification - Varun Narayan Mishra; Vivek Kumar; Rajendra Prasad; Milap Punia (Journal of the Indian Society of Remote Sensing, 2021)

Evaluating hydrogeochemical characteristics of groundwater and surface water in the Upper Pearl River Watershed, USA - Varun Paul; Shannon Vattikuti; Padmanava Dash; Zikri Arslan (Environmental Monitoring and Assessment, 2021)

Climate change scenarios at hourly time‐step over Switzerland from an enhanced temporal downscaling approach - Adrien Michel; Varun Sharma; Michael Lehning; Hendrik Huwald (International Journal of Climatology, 2021)
Many physically‐based models for climate change impact studies require sub‐daily temporal resolution of the forcing data to provide meaningful predictions. However, climate scenarios are typically available at daily time step, severely limiting the application of such physically‐based models. In this study, we propose an enhanced delta‐change method for downscaling climate change scenarios from daily to hourly resolution. The approach presented provides objective criteria for assessing the quality of the determined delta and downscaled time series, while also fixing issues of common quantile mapping methods used for spatial downscaling related to the decrease of correlation between different variables. However, this new approach has limitations in correctly representing statistically extreme events and changes in the frequency of discontinuous events such as precipitation. Smoothing of historical and future data is required prior to applying the delta‐change method, and the related parameters are found to have a subtle impact on the correctness of the representation of the seasonal means as well as the resulting (artificial) variability in the scenario data product. This new method is universal and can be applied with smoothing approaches apart from the harmonic fitting used in this work and in the past. In this study, the assessment suggested the use of seven harmonics for the smoothing of the input data as a best choice of this parameter for the data used. The method is applied to a Swiss climate change scenario data set, CH2018, and to a complement of this set to a Swiss alpine measurement network obtained by spatial transfer of CH2018, resulting in a set of 68 climate change scenarios at hourly resolution for 188 stations over Switzerland significantly expanding upon the spatial and temporal resolution of the CH2018 data set. All source code to perform such an analysis and the complete data product are provided open access.

The Modulatory Effect of Cholesterol Synthesis by Oryza sativa Derived Bioactive Peptide Fractions: An In Vitro Investigation - Varun Kumar; Lakshmy V. Kurup; Purnima Kaul Tiku (International Journal of Peptide Research and Therapeutics, 2021)

Recovery of nanosized silica and lignin from sugarcane bagasse waste and their engineering in fabrication of composite membrane for water purification - Baljinder Singh Kauldhar; Balwinder Singh Sooch; Shushil Kumar Rai; Varun Kumar; Sudesh Kumar Yadav (Environmental Science and Pollution Research, 2021)

Riverine landscape dynamics of the Upper Ganga River (Haridwar-Narora), India - Satish Prasad; Ridhi Saluja; Varun Joshi; J K Garg (Environmental Monitoring and Assessment, 2021)

Quantitative Chemical Profiling of Commercial Glyceride Excipients via 1H NMR Spectroscopy - Isha Saraf; Varun Kushwah; Hansjoerg Weber; Dattatray Modhave; Thean Yeoh; Amrit Paudel (AAPS PharmSciTech, 2021)
Glycerides are the main components of oils, and fats, used in formulated products in the food and cosmetic industry as well as in the pharmaceutical product industry. However, there is limited literature available on the analysis of the chemical composition of glycerides. The lack of a suitable analytical method for complete chemical profiling of glycerides is one of the bottlenecks in understanding and controlling the change in chemical composition during processing, formulation, and storage. Thus, the aim of the present study is to develop a calibration-free quantitative proton nuclear magnetic resonance (qHNMR) method for the simultaneous quantification of different components of glycerides. The qHNMR method was developed for the quantification of mono-, di-, and triglycerides; their positional isomers; free fatty acids; and glycerol content. The accuracy, precision, and robustness of the developed method were evaluated and were found suitable for the quantitative analysis of five batches of marketed excipient. The study demonstrates the potential of qHNMR method for the quantification of different components of glycerides in various marketed products. The method has the ability to identify the variability of glycerides among different batches and suppliers in terms of chemical composition and also to discern the changes during storage.

Multi-class diagnosis of Alzheimer’s disease using cascaded three dimensional-convolutional neural network - Manu Raju; Varun P. Gopi; V. S. Anitha; Khan A. Wahid (Physical and Engineering Sciences in Medicine, 2020)

Tangential winds of a vortex system in a planetary surface layer - Shefali Uttam; Deepak Singh; Varun Sheel (Journal of Earth System Science, 2020)

Heavy metal pollution in surface water of the Upper Ganga River, India: human health risk assessment - Satish Prasad; Ridhi Saluja; Varun Joshi; J. K. Garg (Environmental Monitoring and Assessment, 2020)

Automated classification of diabetic retinopathy through reliable feature selection - S. Gayathri; Varun P. Gopi; P. Palanisamy (Physical and Engineering Sciences in Medicine, 2020)

Automated segmentation of optic disc using statistical region merging and morphological operations - K. S. Nija; C. P. Anupama; Varun P. Gopi; V. S. Anitha (Physical and Engineering Sciences in Medicine, 2020)

Effect of growth hormone gene polymorphism on growth traits in migratory Gaddi goats of Western Himalayas, India - Gitanjli Gitanjli; Varun Sankhyan; Y. P. Thakur; P. K. Dogra (Tropical Animal Health and Production, 2020)

Wireless Pacing Using an Asynchronous Three-Tiered Inductive Power Transfer System - Parinaz Abiri; Arash Abiri; Varun Gudapati; Chih-Chiang Chang; Mehrdad Roustaei; Hamed Bourenane; Usama Anwar; Dejan Markovic; Tzung K. Hsiai (Annals of Biomedical Engineering, 2020)

A Bayesian hierarchical approach to quantifying stakeholder attitudes toward conservation in the presence of reporting error - Divya Vasudev; Varun R. Goswami (Conservation Biology, 2020)
Stakeholder support is vital for achieving conservation success, yet there are few reliable mechanisms to monitor stakeholder attitudes toward conservation. Approaches used to assess attitudes rarely account for bias arising from reporting error, which can lead to falsely reporting a positive attitude toward conservation (false‐positive error) or not reporting a positive attitude when the respondent has a positive attitude toward conservation (false‐negative error). Borrowing from developments in applied conservation science, we used a Bayesian hierarchical model to quantify stakeholder attitudes as the probability of having a positive attitude toward wildlife notionally (or in abstract terms) and at localized scales while accounting for reporting error. We compared estimates from our model, Likert scores, and naïve estimates (i.e., proportion of respondents reporting a positive attitude in at least 1 question that was only susceptible to false‐negative error) with true stakeholder attitudes through simulations. We then applied the model in a survey of tea estate staff on their attitudes toward Asian elephants ( Elephas maximus ) in the Kaziranga–Karbi Anglong landscape of northeast India. In simulations, Bayesian model estimates of stakeholder attitudes toward wildlife were less biased than naïve estimates or Likert scores. After accounting for reporting errors, we estimated the probability of having a positive attitude toward elephants notionally as 0.85 in the Kaziranga landscape, whereas the proportion of respondents who had positive attitudes toward elephants at a localized scale was 0.50. In comparison, without accounting for reporting errors, naïve estimates of proportions of respondents with positive attitudes toward elephants were 0.69 and 0.23 notionally and at local scales, respectively. False (positive and negative) reporting probabilities were consistently not 0 (0.22–0.68). Regular and reliable assessment of stakeholder attitudes–combined with inference on drivers of positive attitudes–can help assess the success of initiatives aimed at facilitating human behavioral change and inform conservation decision making.

Bioprospecting potential of microbial communities in solid waste landfills for novel enzymes through metagenomic approach - Karnika Thakur; Manisha Chownk; Varun Kumar; Anjali Purohit; Alokika Vashisht; Vinod Kumar; Sudesh Kumar Yadav (World Journal of Microbiology and Biotechnology, 2020)

Effects of a High Temperature (500 °C) on the Fracture Processes in Calcite-Cemented Sandstone Along Bedding-Plane Orientations - Varun Maruvanchery; Eunhye Kim (Rock Mechanics and Rock Engineering, 2020)

The effects of autistic traits and academic degree on visuospatial abilities - Massimiliano Conson; Vincenzo Paolo Senese; Chiara Baiano; Isa Zappullo; Varun Warrier; Sara Salzano; Monica Positano; Simon Baron-Cohen (Cognitive Processing, 2020)

A study of comorbidities in myasthenia gravis - Usha K. Misra; Jayantee Kalita; Varun K. Singh; Surendra Kumar (Acta Neurologica Belgica, 2020)

Numerical Modeling of Discrete Fractures in a Field-Scale FORGE EGS Reservoir - Azadeh Riahi; Will Pettitt; Branko Damjanac; Varun; Derrick Blanksma (Rock Mechanics and Rock Engineering, 2019)

Women as Drivers of Change for Nutrition-Sensitive Agriculture: Case Study of a Novel Extension Approach in Wardha, India - R Rukmani; R. Gopinath; G. Anuradha; R. Sanjeev; Varun Kumar Yadav (Agricultural Research, 2019)

A non-beta-lactam antibiotic inhibitor for enterohemorrhagic Escherichia coli O104:H4 - Haoqi Wang; Arul Jayaraman; Rani Menon; Varun Gejji; R. Karthikeyan; Sandun Fernando (Journal of Molecular Medicine, 2019)

EDTA-Assisted Metal Uptake in Raphanus sativus L. and Brassica oleracea L.: Assessment of Toxicity and Food Safety - Ritu Chaturvedi; Paulo Favas; João Pratas; Mayank Varun; Manoj S. Paul (Bulletin of Environmental Contamination and Toxicology, 2019)

Retrieval of Martian ozone and dust from SPICAM spectrometer for MY27–MY28 - Ashimananda Modak; Varun Sheel; Franck Montmessin (Journal of Earth System Science, 2019)

Mechanics of controlled release of insulin entrapped in polyacrylic acid gels via variable electrical stimuli - Samavath Mallawarachchi; Aishwarya Mahadevan; Varun Gejji; Sandun Fernando (Drug Delivery and Translational Research, 2019)

The influence of local meteorology and convection on carbon monoxide distribution over Chennai - L K Sahu; Nidhi Tripathi; Varun Sheel; N Ojha (Journal of Earth System Science, 2019)

Design and Toxicity Evaluation of Novel Fatty Acid-Amino Acid-Based Biocompatible Surfactants - Sameer S. Katiyar; Varun Kushwah; Chander Parkash Dora; Ravindra Y. Patil; Sanyog Jain (AAPS PharmSciTech, 2019)

Design and analysis for the removal of active pharmaceutical residues from synthetic wastewater stream - Chinmoy Deb; Bonny Thawani; Sujith Menon; Varun Gore; Vijayalakshmi Chellappan; Shivendu Ranjan; Mahesh Ganesapillai (Environmental Science and Pollution Research, 2019)

Genetic variant rs10937405 of TP63 and susceptibility to lung cancer risk in north Indian population - GH. Rasool Bhat; Amrita Bhat; Sonali Verma; Itty Sethi; Ruchi Shah; Varun Sharma; S. Minerva; Divya Bakshi; Bhanu Sharma; Sandeep Koul; Deepak Abrol; Audesh Bhat; et al. (Journal of Genetics, 2019)

Evaluation of anti-dengue activity of Carica papaya aqueous leaf extract and its role in platelet augmentation - Navita Sharma; Kamla Prasad Mishra; Sudipta Chanda; Varun Bhardwaj; Himanshi Tanwar; Lilly Ganju; Bhuvnesh Kumar; Shashi Bala Singh (Archives of Virology, 2019)

Polyglutamic Acid Functionalization of Chitosan Nanoparticles Enhances the Therapeutic Efficacy of Insulin Following Oral Administration - Dileep Urimi; Ashish Kumar Agrawal; Varun Kushwah; Sanyog Jain (AAPS PharmSciTech, 2019)

Performance evaluation of textural features in improving land use/land cover classification accuracy of heterogeneous landscape using multi-sensor remote sensing data - Varun Narayan Mishra; Rajendra Prasad; Praveen Kumar Rai; Ajeet Kumar Vishwakarma; Aman Arora (Earth Science Informatics, 2019)

Oral Delivery of Methylthioadenosine to the Brain Employing Solid Lipid Nanoparticles: Pharmacokinetic, Behavioral, and Histopathological Evidences - Pramod Kumar; Gajanand Sharma; Varun Gupta; Ramanpreet Kaur; Kanika Thakur; Ruchi Malik; Anil Kumar; Naveen Kaushal; Om Prakash Katare; Kaisar Raza (AAPS PharmSciTech, 2019)

Blank spots on the map: some current questions on nuclear organization and genome architecture - Carmen Adriaens; Leonid A. Serebryannyy; Marina Feric; Andria Schibler; Karen J. Meaburn; Nard Kubben; Pawel Trzaskoma; Sigal Shachar; Sandra Vidak; Elizabeth H. Finn; Varun Sood; Gianluca Pegoraro; et al. (Histochemistry and Cell Biology, 2018)

Atmospheric abundance of HULIS during wintertime in Indo-Gangetic Plain: impact of biomass burning emissions - Varun Kumar; Prashant Rajput; Anubha Goel (Journal of Atmospheric Chemistry, 2018)

Amphotericin B Loaded Chitosan Nanoparticles: Implication of Bile Salt Stabilization on Gastrointestinal Stability, Permeability and Oral Bioavailability - Sanyog Jain; Chamala Siva Kumar Reddy; Rajan Swami; Varun Kushwah (AAPS PharmSciTech, 2018)

Development of CGMS system in ridge gourd [Luffa acutangula (Roxb.) L.] for production of F1 hybrids - T. Pradeepkumar; J. S. Minimol; Deepu Mathew; K. Veni; C. Varun Roch; P. G. Chithira; Rajeshwary Unni (Euphytica, 2018)

Water resource management using geothermal energy: Eritrea - Dornadula Chandrasekharam; Aref Lashin; Nassir Al Arifi; Abdulaziz Al-Bassam; Varun Chandrasekhar (Arabian Journal of Geosciences, 2018)

Prediction of spatio-temporal land use/land cover dynamics in rapidly developing Varanasi district of Uttar Pradesh, India, using geospatial approach: a comparison of hybrid models - Varun Narayan Mishra; Praveen Kumar Rai; Rajendra Prasad; Milap Punia; Mărgărit-Mircea Nistor (Applied Geomatics, 2018)

Ground Based Bistatic Scatterometer Measurement for the Estimation of Growth Variables of Ladyfinger Crop at X-Band - Ajeet Kumar Vishwakarma; Rajendra Prasad; Dileep Kumar Gupta; Pradeep Kumar; Varun Narayan Mishra (Journal of the Indian Society of Remote Sensing, 2018)

Novel cationic supersaturable nanomicellar systems of raloxifene hydrochloride with enhanced biopharmaceutical attributes - Atul Jain; Rajpreet Kaur; Sarwar Beg; Varun Kushwah; Sanyog Jain; Bhupinder Singh (Drug Delivery and Translational Research, 2018)

Citrus Epicarp-Derived Biochar Reduced Cd Uptake and Ameliorates Oxidative Stress in Young Abelmoschus esculentus (L.) Moench (okra) Under Low Cd Stress - Clement O. Ogunkunle; Mayank Varun; Iyanuoluwa G. Ogundele; Kehinde S. Olorunmaiye; Manoj S. Paul (Bulletin of Environmental Contamination and Toxicology, 2018)

Lyotropic Liquid Crystalline Nanoparticles of Amphotericin B: Implication of Phytantriol and Glyceryl Monooleate on Bioavailability Enhancement - Sanyog Jain; Pooja Yadav; Rajan Swami; Nitin Kumar Swarnakar; Varun Kushwah; Sameer S. Katiyar (AAPS PharmSciTech, 2018)

Nitrogen fixation ability explains leaf chemistry and arbuscular mycorrhizal responses to fertilization - Yadugiri V. Tiruvaimozhi; Varun Varma; Mahesh Sankaran (Plant Ecology, 2018)

Studies on biogas-fuelled compression ignition engine under dual fuel mode - Sunil Kumar Mahla; Varun Singla; Sarbjot Singh Sandhu; Amit Dhir (Environmental Science and Pollution Research, 2018)

Agent-based geosimulation for assessment of urban emergency response plans - Mainak Bandyopadhyay; Varun Singh (Arabian Journal of Geosciences, 2018)

Global and regional evaluation of a global model simulated AODs with AERONET and MODIS observations - Varun Sheel; Raj P. Guleria; S. Ramachandran (International Journal of Climatology, 2018)
Aerosol optical properties vary widely globally due to their short residence time and the large variability in their composition and size resulting from varying sources. In this study, we make use of the three‐dimensional global atmospheric chemistry transport model MOZART (Model for OZone And Related chemical Tracers), to simulate Aerosol Optical Depths (AODs) and compare with observations from MODIS (Moderate Resolution Imaging Spectroradiometer, level‐3) on board the Terra satellite and AERONET (AErosol RObotic NETwork level‐2), at regional and global scale for the period 2000–2007. The AOD values at a reference wavelength 550 nm are reported for all the data sets. Model and observations show intense aerosol burden over the parts of the world where developing countries are located. On a regional scale, varying features are noted for different regions depending upon topography, regional emissions and weather conditions. MOZART captures the general features observed in AERONET and MODIS fairly well; however, in biomass burning dominated regions (Central South America, South Africa, and North Australia) it underestimates the observed AOD. In industrial regions (North Europe and Mediterranean) MOZART overestimates the observations and over dust dominant regions (Saharan Africa, Middle East, and East Asia), the model AODs are comparable to AERONET and MODIS observations. In general, MOZART simulated AOD show similar seasonal and regional variability as observed in AERONET and MODIS. Our results are similar to the most commonly used models, i.e. GOCART (the GOddard Chemistry, Aerosol, Radiation, and Transport) and GEOS‐4 (Goddard Earth Observing System‐version 4).

Reconstructing the demographic history of the Himalayan and adjoining populations - Rakesh Tamang; Gyaneshwer Chaubey; Amrita Nandan; Periyasamy Govindaraj; Vipin Kumar Singh; Niraj Rai; Chandana Basu Mallick; Vishwas Sharma; Varun Kumar Sharma; Anish M. Shah; Albert Lalremruata; Alla G. Reddy; et al. (Human Genetics, 2018)

Neuroleptic malignant syndrome as a presenting feature of subacute sclerosing panencephalitis - Divyani Garg; Varun Reddy; Rajesh Kumar Singh; Deepa Dash; Rohit Bhatia; Manjari Tripathi (Journal of NeuroVirology, 2018)

Improved Oral Bioavailability, Therapeutic Efficacy, and Reduced Toxicity of Tamoxifen-Loaded Liquid Crystalline Nanoparticles - Sanyog Jain; B. Heeralal; Rajan Swami; Nitin K. Swarnakar; Varun Kushwah (AAPS PharmSciTech, 2018)

A molecular insight into papaya leaf curl—a severe viral disease - Priyanka Varun; S. A. Ranade; Sangeeta Saxena (Protoplasma, 2017)

Novel Gemcitabine Conjugated Albumin Nanoparticles: a Potential Strategy to Enhance Drug Efficacy in Pancreatic Cancer Treatment - Varun Kushwah; Ashish Kumar Agrawal; Chander Parkash Dora; David Mallinson; Dimitrios A. Lamprou; Ramesh C. Gupta; Sanyog Jain (Pharmaceutical Research, 2017)

Stable Co-crystals of Glipizide with Enhanced Dissolution Profiles: Preparation and Characterization - Narendra Kumar Pandey; Hans Raj Sehal; Varun Garg; Tejasvi Gaur; Bimlesh Kumar; Sachin Kumar Singh; Monica Gulati; K. Gowthamarajan; Palak Bawa; Sarvi Yadav Rajesh; Parth Sharma; Rakesh Narang (AAPS PharmSciTech, 2017)

Leopard–Human Conflict Led Casualties and Conservation Awareness Campaign in Shivalik Hills of Northern India - Pradeep Kumar; Sangeeta Chandel; Vijay Kumar; Varun Sankhyan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Improved Stability and Enhanced Oral Bioavailability of Atorvastatin Loaded Stearic Acid Modified Gelatin Nanoparticles - Deepanshu Shilpi; Varun Kushwah; Ashish Kumar Agrawal; Sanyog Jain (Pharmaceutical Research, 2017)

Erratum to: Behavioural and Electrophysiological Responses of Mosquito Vectors Aedes aegypti, Anopheles stephensi and Culex quinquefasciatus to an Ethyl Ester: Ethyl 2-Aminobenzoate - Johirul Islam; Sunil Dhiman; Varun Tyagi; Sanjukta Duarah; Kamaruz Zaman; Pronobesh Chattopadhyay (Journal of Insect Behavior, 2017)

Behavioural and Electrophysiological Responses of Mosquito Vectors Aedes aegypti, Anopheles stephensi and Culex quinquefasciatus to an Ethyl Ester: Ethyl 2-aminobenzoate - Johirul Islam; Sunil Dhiman; Varun Tyagi; Sanjukta Duarah; Kamaruz Zaman; Pronobesh Chattopadhyay (Journal of Insect Behavior, 2017)

Impact of tropical convection and ENSO variability in vertical distributions of CO and O3 over an urban site of India - L. K. Sahu; Varun Sheel; M. Kajino; M. Deushi; Sachin S. Gunthe; P. R. Sinha; Ravi Yadav; Devendra Pal; P. Nedelec; Valérie Thouret; Herman G. Smit (Climate Dynamics, 2017)

Estimation of Upper Limit of Normal for Serum Alanine Transaminase in Healthy South Indian Population - Pazhanivel Mohan; Varun Sundar; Emmanuel Bhaskar; Syluvai Anthony (Indian Journal of Clinical Biochemistry, 2017)

Identification of Sesbania sesban (L.) Merr. as an Efficient and Well Adapted Phytoremediation Tool for Cd Polluted Soils - Mayank Varun; Clement O. Ogunkunle; Rohan D’Souza; Paulo Favas; Manoj Paul (Bulletin of Environmental Contamination and Toxicology, 2017)

Comparative Study of Two ELISA Kits for Estimation of Antibodies to Hepatitis B Virus in Human Normal Immunoglobulin and Specific Immunoglobulin Intended for Intravenous or Intramuscular Use - J. P. Prasad; Y. Madhu; Arushi Mandhan; Payal Garg; Anu Prakash; Varsha Singh; Daud Ali; Prdeep Kumar; Surinder Singh; G. R. Soni; Varun Singh (Indian Journal of Clinical Biochemistry, 2017)

Are Cystic Fibrosis Aspergillus fumigatus Isolates Different? Intermicrobial Interactions with Pseudomonas - Hasan Nazik; Richard B. Moss; Vyshnavi Karna; Karl V. Clemons; Niaz Banaei; Kevin Cohen; Varun Choudhary; David A. Stevens (Mycopathologia, 2017)

Desalination of Seawater using Geothermal Energy to Meet Future Fresh Water Demand of Saudi Arabia - D. Chandrasekharam; A. Lashin; N. Al Arifi; A. Al Bassam; C. Varun (Water Resources Management, 2017)

Comparative whole-transcriptome analysis in Podophyllum species identifies key transcription factors contributing to biosynthesis of podophyllotoxin in P. hexandrum - Pawan Kumar; Varun Jaiswal; Tarun Pal; Jagdish Singh; Rajinder S. Chauhan (Protoplasma, 2017)

TNF-α and IL-6 inhibitory effects of cyclic dipeptides isolated from marine bacteria Streptomyces sp - Yedukondalu Nalli; Shilpa Gupta; Vidushi Khajuria; Varun P. Singh; Mehak Sajgotra; Zabeer Ahmed; Narsinh L. Thakur; Asif Ali (Medicinal Chemistry Research, 2017)

Biosynthesis and therapeutic implications of iridoid glycosides from Picrorhiza genus: the road ahead - Varun Kumar; Rajinder Singh Chauhan; Chanderdeep Tandon (Journal of Plant Biochemistry and Biotechnology, 2017)

Systematic Development of Transethosomal Gel System of Piroxicam: Formulation Optimization, In Vitro Evaluation, and Ex Vivo Assessment - Varun Garg; Harmanpreet Singh; Amit Bhatia; Kaisar Raza; Sachin Kumar Singh; Bhupinder Singh; Sarwar Beg (AAPS PharmSciTech, 2017)

Modulation of Picroside-I Biosynthesis in Grown Elicited Shoots of Picrorhiza kurroa In Vitro - Neha Sharma; Varun Kumar; Rajinder Singh Chauhan; Hemant Sood (Journal of Plant Growth Regulation, 2016)

Nanocurcumin accords protection against acute hypobaric hypoxia induced lung injury in rats - Sarita Nehra; Varun Bhardwaj; Anju Bansal; Deepika Saraswat (Journal of Physiology and Biochemistry, 2016)

Higher amount of steviol detected in the leaves of a non-toxic endangered medicinal herb, Aconitum heterophyllum - Varun Kumar; Rajinder Singh Chauhan (Journal of Plant Biochemistry and Biotechnology, 2016)

Ecological vulnerability assessment of trace metals in topsoil around a newly established metal scrap factory in southwestern Nigeria: geochemical, geospatial and exposure risk analyses - Clement O. Ogunkunle; Mayank Varun; Oluwanishola F. Dawodu; Olusegun O. Awotoye; Paul O. Fatoba (Rendiconti Lincei. Scienze Fisiche e Naturali, 2016)

Insights into horizontal acquisition patterns of dormancy and reactivation regulon genes in mycobacterial species using a partitioning-based framework - Varun Mehra; Tarini Shankar Ghosh; Sharmila S Mande (Journal of Biosciences, 2016)

Breeding Round Fruited Brinjal for Export from Eastern India - Varun Durwas Shende; Arup Chattopadhyay; Yogendra Yadav; Tania Seth; Subhra Mukherjee (Agricultural Research, 2016)

Transgranular Crack Nucleation in Carrara Marble of Brittle Failure - Yi Cheng; Louis Ngai Yuen Wong; Varun Maruvanchery (Rock Mechanics and Rock Engineering, 2016)

Effects of nutrient addition and soil drainage on germination of N-fixing and non-N-fixing tropical dry forest tree species - Varun Varma; Siddharth B. Iyengar; Mahesh Sankaran (Plant Ecology, 2016)

Different Lithological Varieties of Bukit Timah Granite in Singapore: a Preliminary Comparison Study on Engineering Properties - Louis Ngai Yuen Wong; Varun Maruvanchery (Rock Mechanics and Rock Engineering, 2016)

Anticancer activity of Ophiobolin A, isolated from the endophytic fungus Bipolaris setariae - Dimple R. Bhatia; Payal Dhar; Varun Mutalik; Sunil Kumar Deshmukh; Shilpa A. Verekar; Dattatraya C. Desai; Rajendra Kshirsagar; Padma Thiagarajan; Veena Agarwal (Natural Product Research, 2016)

Optimization of a preparative RP-HPLC method for isolation and purification of picrosides in Picrorhiza kurroa - Varun Kumar; Hemant Sood; Rajinder Singh Chauhan (Journal of Plant Biochemistry and Biotechnology, 2016)

Tracking dynamics of enzyme activities and their gene expression in Picrorhiza kurroa with respect to picroside accumulation - Varun Kumar; Kirti Shitiz; Rajinder Singh Chauhan; Hemant Sood; Chanderdeep Tandon (Journal of Plant Biochemistry and Biotechnology, 2016)

A remote sensing aided multi-layer perceptron-Markov chain analysis for land use and land cover change prediction in Patna district (Bihar), India - Varun Narayan Mishra; Praveen Kumar Rai (Arabian Journal of Geosciences, 2016)

c-Fos Protects Neurons Through a Noncanonical Mechanism Involving HDAC3 Interaction: Identification of a 21-Amino Acid Fragment with Neuroprotective Activity - Varun Rawat; Warren Goux; Marc Piechaczyk; Santosh R. D′Mello (Molecular Neurobiology, 2016)

Modeling population heterogeneity in viral dynamics for chronic hepatitis C infection: Insights from Phase 3 telaprevir clinical studies - Eric L. Haseltine; Holly Kimko; Haobin Luo; John Tolsma; Doug J. Bartels; Tara L. Kieffer; Varun Garg (Journal of Pharmacokinetics and Pharmacodynamics, 2015)

An insight into conflux of metabolic traffic leading to picroside-I biosynthesis by tracking molecular time course changes in a medicinal herb, Picrorhiza kurroa - Varun Kumar; Neha Sharma; Kirti Shitiz; Tiratha Raj Singh; Chanderdeep Tandon; Hemant Sood; Rajinder Singh Chauhan (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Cost effective quantification of picrosides in Picrorhiza kurroa by employing response surface methodology using HPLC-UV - Varun Kumar; Varun Kumar; Rajinder Singh Chauhan; Hemant Sood; Chanderdeep Tandon (Journal of Plant Biochemistry and Biotechnology, 2015)

Regional biomass burning trends in India: Analysis of satellite fire data - L K Sahu; Varun Sheel; Kumud Pandey; Ravi Yadav; P Saxena; Sachin Gunthe (Journal of Earth System Science, 2015)

Expression analysis of biosynthetic pathway genes vis-à-vis podophyllotoxin content in Podophyllum hexandrum Royle - Pawan Kumar; Tarun Pal; Neha Sharma; Varun Kumar; Hemant Sood; Rajinder S. Chauhan (Protoplasma, 2015)

White Light Emission Through Downconversion of Terbium and Europium Doped CeF3 Nanophosphors - S Varun; Mohit Kalra; Mayuri Gandhi (Journal of Fluorescence, 2015)

Detection of intermediates through high-resolution mass spectrometry for constructing biosynthetic pathways for major chemical constituents in a medicinally important herb, Swertia chirayita - Varun Kumar; Hemant Sood; Rajinder Singh Chauhan (Natural Product Research, 2015)

Abutilon indicum L.: a prospective weed for phytoremediation - Mayank Varun; Disha Jaggi; Rohan D’Souza; Manoj S. Paul; Bhumesh Kumar (Environmental Monitoring and Assessment, 2015)

Mechanistic understanding of human–wildlife conflict through a novel application of dynamic occupancy models - Varun R. Goswami; Kamal Medhi; James D. Nichols; Madan K. Oli (Conservation Biology, 2015)
Crop and livestock depredation by wildlife is a primary driver of human–wildlife conflict, a problem that threatens the coexistence of people and wildlife globally. Understanding mechanisms that underlie depredation patterns holds the key to mitigating conflicts across time and space. However, most studies do not consider imperfect detection and reporting of conflicts, which may lead to incorrect inference regarding its spatiotemporal drivers. We applied dynamic occupancy models to elephant crop depredation data from India between 2005 and 2011 to estimate crop depredation occurrence and model its underlying dynamics as a function of spatiotemporal covariates while accounting for imperfect detection of conflicts. The probability of detecting conflicts was consistently t would not be raided in primary period t + 1 varied with elevation gradient in different seasons and was influenced negatively by mean rainfall and village density and positively by distance to forests. Negative effects of rainfall variation and distance to forests best explained variation in the probability that sites not raided by elephants in primary period t would be raided in primary period t + 1. With our novel application of occupancy models, we teased apart the spatiotemporal drivers of conflicts from factors that influence how they are observed, thereby allowing more reliable inference on mechanisms underlying observed conflict patterns. We found that factors associated with increased crop accessibility and availability (e.g., distance to forests and rainfall patterns) were key drivers of elephant crop depredation dynamics. Such an understanding is essential for rigorous prediction of future conflicts, a critical requirement for effective conflict management in the context of increasing human–wildlife interactions.

Hydrogen sulfide mitigates homocysteine-mediated pathological remodeling by inducing miR-133a in cardiomyocytes - Varun Kesherwani; Shyam Sundar Nandi; Surender K. Sharawat; Hamid R. Shahshahan; Paras Kumar Mishra (Molecular and Cellular Biochemistry, 2015)

Nanocurcumin protects cardiomyoblasts H9c2 from hypoxia-induced hypertrophy and apoptosis by improving oxidative balance - Sarita Nehra; Varun Bhardwaj; Namita Kalra; Lilly Ganju; Anju Bansal; Shweta Saxena; Deepika Saraswat (Journal of Physiology and Biochemistry, 2015)

A Systematic Assessment of the Use of Platelet-Rich Plasma in Spinal Fusion - Benjamin D. Elder; Christina Holmes; C. Rory Goodwin; Sheng-Fu Lo; Varun Puvanesarajah; Thomas A. Kosztowski; John E. Locke; Timothy F. Witham (Annals of Biomedical Engineering, 2015)

An efficient synthesis and antimicrobial screening of new hybrid molecules containing coumarin and indenopyridine moiety - Dinkar I. Brahmbhatt; Chirag V. Patel; Varun G. Bhila; Niraj H. Patel; Apoorva A. Patel (Medicinal Chemistry Research, 2015)

Influence of gamma rays and ethyl methane sulphonate (EMS) on the levels of phytic acid, raffinose family oligosaccharides and antioxidants in soybean seeds of different genotypes - Awadhesh Kumar; Varun Kumar; S. K. Lal; Monica Jolly; Archana Sachdev (Journal of Plant Biochemistry and Biotechnology, 2015)

Comparison of support vector machine, artificial neural network, and spectral angle mapper algorithms for crop classification using LISS IV data - Pradeep Kumar; Dileep Kumar Gupta; Varun Narayan Mishra; Rajendra Prasad (International Journal of Remote Sensing, 2015)

Acaricidal activity of ethanolic extract of Artemisia absinthium against Hyalomma anatolicum ticks - R. Godara; S. Parveen; R. Katoch; A. Yadav; M. Katoch; J. K. Khajuria; D. Kaur; A. Ganai; P. K. Verma; Varun Khajuria; N. K. Singh (Experimental and Applied Acarology, 2015)

Quantitative structure–activity relationship (QSAR) studies as strategic approach in drug discovery - Harun M. Patel; Malleshappa N. Noolvi; Poonam Sharma; Varun Jaiswal; Sumit Bansal; Sandeep Lohan; Suthar Sharad Kumar; Vikrant Abbot; Saurabh Dhiman; Varun Bhardwaj (Medicinal Chemistry Research, 2014)

Mining whole genomes and transcriptomes of Jatropha (Jatropha curcas) and Castor bean (Ricinus communis) for NBS-LRR genes and defense response associated transcription factors - Archit Sood; Varun Jaiswal; Sree Krishna Chanumolu; Nikhil Malhotra; Tarun Pal; Rajinder Singh Chauhan (Molecular Biology Reports, 2014)

Asymmetric Cell–Matrix and Biomechanical Abnormalities in Elastin Insufficiency Induced Aortopathy - Varun K. Krishnamurthy; Ashlie N. Evans; Janaka P. Wansapura; Hanna Osinska; Kelsey E. Maddy; Stefanie V. Biechler; Daria A. Narmoneva; Richard L. Goodwin; Robert B. Hinton (Annals of Biomedical Engineering, 2014)

Fumarate metabolism and ATP production in Pseudomonas fluorescens exposed to nitrosative stress - Varun P. Appanna; Christopher Auger; Sean C. Thomas; Abdelwahab Omri (Antonie van Leeuwenhoek, 2014)

Rainfall variability and indices of extreme rainfall-analysis and perception study for two stations over Central Himalaya, India - Sneh Joshi; Kireet Kumar; Varun Joshi; Bimal Pande (Natural Hazards, 2014)

Spatio-temporal variation of biomass burning sources over South and Southeast Asia - L. K. Sahu; Varun Sheel (Journal of Atmospheric Chemistry, 2014)

Black Spot: a platform for automated and rapid estimation of leaf area from scanned images - Varun Varma; Anand M. Osuri (Plant Ecology, 2013)

Results of FDA’s First Interlaboratory Computational Study of a Nozzle with a Sudden Contraction and Conical Diffuser - Sandy F. C. Stewart; Prasanna Hariharan; Eric G. Paterson; Greg W. Burgreen; Varun Reddy; Steven W. Day; Matthew Giarra; Keefe B. Manning; Steven Deutsch; Michael R. Berman; Matthew R. Myers; Richard A. Malinauskas (Cardiovascular Engineering and Technology, 2013)

One pot synthesis of some novel coumarins containing 5-(substituted-2-hydroxybenzoyl) pyridine as a new class of antimicrobial and antituberculosis agents - Varun G. Bhila; Chirag V. Patel; Niraj H. Patel; Dinkar I. Brahmbhatt (Medicinal Chemistry Research, 2013)

A rapid rotation to an inverted seated posture inhibits muscle force, activation, heart rate and blood pressure - Pramod Johar; Varun Grover; Mario C. DiSanto; Duane C. Button; David G. Behm (European Journal of Applied Physiology, 2013)

The first multituberculate mammal from India - Varun Parmar; Guntupalli V. R. Prasad; Deepak Kumar (The Science of Nature, 2013)

Synthesis, characterization and biological evaluation of some pyridine and quinoline fused chromenone derivatives - Mehul A. Patel; Varun G. Bhila; Niraj H. Patel; Anil K. Patel; Dinker I. Brahmbhatt (Medicinal Chemistry Research, 2012)

Antifertility activity of methanolic bark extract of Aegle marmelos (l.) in male wistar rats - Shyam S Agrawal; Ashok Kumar; Sumeet Gullaiya; Vishal Dubey; Ashish Nagar; Poonam Tiwari; Parul Dhar; Varun Singh (DARU Journal of Pharmaceutical Sciences, 2012)

Assessment of CFD Performance in Simulations of an Idealized Medical Device: Results of FDA’s First Computational Interlaboratory Study - Sandy F. C. Stewart; Eric G. Paterson; Greg W. Burgreen; Prasanna Hariharan; Matthew Giarra; Varun Reddy; Steven W. Day; Keefe B. Manning; Steven Deutsch; Michael R. Berman; Matthew R. Myers; Richard A. Malinauskas (Cardiovascular Engineering and Technology, 2012)

Effects of salicylic acid on seedling growth and nitrogen use efficiency in cucumber ( Cucumis sativus L.) - Pramod Kumar Singh; Varun Kumar Chaturvedi (Plant Biosystems, 2012)

Assessment of the sensitizing potential of textile disperse dyes and some of their metabolites by the loose-fit coculture-based sensitization assay (LCSA) - Anna Sonnenburg; Varun Ahuja; Maximilian Schreiner; Thomas Platzek; Ralf Stahlmann (Archives of Toxicology, 2012)

Human control of climate change - Varun Dutt; Cleotilde Gonzalez (Climatic Change, 2012)

Genetic diversity analysis of Tinospora cordifolia germplasm collected from northwestern Himalayan region of India - VIJAY RANA; KALPANA THAKUR; RITU SOOD; VARUN SHARMA; T. R. SHARMA (Journal of Genetics, 2012)

Metal contamination of soils and plants associated with the glass industry in North Central India: prospects of phytoremediation - Mayank Varun; Rohan D’Souza; João Pratas; Manoj S. Paul (Environmental Science and Pollution Research, 2012)

Bioassay as monitoring system for lead phytoremediation through Crinum asiaticum L. - Mayank Varun; Rohan D’Souza; Devendra Kumar; Manoj S. Paul (Environmental Monitoring and Assessment, 2011)

Phytoextraction Potential of Prosopis juliflora (Sw.) DC. with Specific Reference to Lead and Cadmium - Mayank Varun; Rohan D’Souza; João Pratas; M. S. Paul (Bulletin of Environmental Contamination and Toxicology, 2011)

Neuronal model with distributed delay: analysis and simulation study for gamma distribution memory kernel - Karmeshu; Varun Gupta; K. V. Kadambari (Biological Cybernetics, 2011)

Are all seeds equal? Spatially explicit comparisons of seed fall and sapling recruitment in a tropical forest - Varun Swamy; John Terborgh; Kyle G. Dexter; Benjamin D. Best; Patricia Alvarez; Fernando Cornejo (Ecology Letters, 2011)
Ecology Letters (2011) 14: 195–201 Abstract Understanding demographic transitions may provide the key to explain the high diversity of tropical tree communities. In a faunally intact Amazonian forest, we compared the spatial distribution of saplings of 15 common tree species with patterns of conspecific seed fall, and examined the seed‐to‐sapling transition in relation to locations of conspecific trees. In all species, the spatial pattern of sapling recruitment bore no resemblance to predicted distributions based on the density of seed fall. Seed efficiency (the probability of a seed producing a sapling) is strongly correlated with distance from large conspecific trees, with a > 30‐fold multiplicative increase between recruitment zones that are most distant vs. proximal to conspecific adults. The striking decoupling of sapling recruitment and conspecific seed density patterns indicates near‐complete recruitment failure in areas of high seed density located around reproductive adults. Our results provide strong support for the spatially explicit predictions of the Janzen–Connell hypothesis.

Evaluation of biotechnology-derived novel proteins for the risk of food-allergic potential: advances in the development of animal models and future challenges - Varun Ahuja; Maria Quatchadze; Vaishali Ahuja; Daniela Stelter; Achim Albrecht; Ralf Stahlmann (Archives of Toxicology, 2010)

Relevance of Helicobacter pylori genotypes in gastric pathology and its association with plasma malondialdehyde and nitric oxide levels - Santosh K. Tiwari; G. Manoj; Vishwas Sharma; G. Sivaram; R. Saikant; Avinash Bardia; Varun K. Sharma; Zakia Abid; Aleem A. Khan; M. Aejaz Habeeb; C. M. Habibullah; B. Santhosh Kumar; et al. (Inflammopharmacology, 2010)

Molecular modeling studies, synthesis, and biological evaluation of Plasmodium falciparum enoyl-acyl carrier protein reductase (PfENR) inhibitors - Varun A. Morde; Mushtaque S. Shaikh; Raghuvir R. S. Pissurlenkar; Evans C. Coutinho (Molecular Diversity, 2009)

Appraisal of the sensitising potential of orally and dermally administered Mercaptobenzothiazol by a biphasic protocol of the local lymph node assay - Varun Ahuja; Reinhard Wanner; Thomas Platzek; Ralf Stahlmann (Archives of Toxicology, 2009)

Investigation of the sensitising and cross-sensitising potential of textile dyes and β-lactam antibiotics using a biphasic mice local lymph node assay - Varun Ahuja; Clemens Schreiber; Thomas Platzek; Ralf Stahlmann (Archives of Toxicology, 2009)

A novel role of BELL1-like homeobox genes, PENNYWISE and POUND-FOOLISH, in floral patterning - Lifeng Yu; Varun Patibanda; Harley M. S. Smith (Planta, 2009)

Immunomodulator Effect of Picroliv and its Potential in Treatment Against Resistant Plasmodium yoelii (MDR) Infection in Mice - Varun Dwivedi; Arif Khan; Azevedo Vasco; Nishat Fatima; Vishal Kumar Soni; Anil Dangi; Shailja Misra-Bhattacharya; Mohammad Owais (Pharmaceutical Research, 2008)

Production of TNF-α, IL-1β, IL-12 and IFN-γ in murine peritoneal macrophages on treatment with wheat germ agglutinin in vitro: involvement of tyrosine kinase pathways - Ajit Sodhi; Varun Kesherwani (Glycoconjugate Journal, 2007)

Macroinvertebrate and Fish Populations in a Restored Impounded Salt Marsh 21 Years After the Reestablishment of Tidal Flooding - VARUN SWAMY; PAUL E. FELL; MISHA BODY; MICHAEL B. KEANEY; MAWULI K. NYAKU; ELIZABETH C. MCILVAIN; ALICE L. KEEN (Environmental Management, 2002)

A preliminary report on the role of yoga asanas on oxidative stress in non-insulin dependent diabetes mellitus - Savita Singh; Varun Malhotra; K. P. Singh; S. B. Sharma; S. V. Madhu; O. P. Tandon (Indian Journal of Clinical Biochemistry, 2001)